Superwetting surface and its preparation method and application

Microwave-induced grafting of organic acids and lipophilic monomers on polypropylene surfaces creates durable, stable superwet surfaces with enhanced hydrophilicity and lipophilicity, addressing the limitations of existing methods and improving membrane performance.

JP7602533B2Active Publication Date: 2024-12-18CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2022512344
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-08-23
Filing Date
2020-08-04
Publication Date
2024-12-18
Estimated Expiration
2040-08-04

AI Technical Summary

Technical Problem

Current methods for preparing superhydrophilic and superamphiphilic polymer surfaces are difficult and often require the use of inorganic particles, leading to brittleness and limited application in flexible articles, while existing membrane materials like polypropylene suffer from hydrophobicity issues causing high energy consumption and fouling.

Method used

A method involving microwave irradiation of polypropylene surfaces with organic acids and derivatives, such as maleic anhydride, and lipophilic monomers like vinyl silicone oil, without initiators, to create micro-nanostructured surfaces with superhydrophilic and superoleophilic properties, enhancing both hydrophilicity and lipophilicity.

Benefits of technology

The method results in durable, stable superwet surfaces with improved water and oil flux through membranes, reducing energy consumption and fouling, suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007602533000001
    Figure 0007602533000001
  • Figure 0007602533000002
    Figure 0007602533000002
Patent Text Reader

Abstract

The present invention provides a superwetting surface, a preparation method thereof, and applications thereof. The superwetting surface is a micro-nanostructured polypropylene surface grafted with hydrophilic side groups, where the superwetting surface is at least superhydrophilic and contains no initiator residues. The superwetting surface is prepared by grafting side group-forming monomers onto a micro-nanostructured polypropylene surface as a graft base using microwave irradiation in the absence of an initiator. The preparation method of the present invention is simple, easy to operate, requires simple equipment, is low-cost, and is easily industrialized. In preparing the superwetting surface, the molecular weight of the polypropylene is not reduced after grafting, neither residual monomers nor initiator residues are present, and the superwetting effect of the resulting surface is sustained and stable. The superwetting surface can be used in bonding, spraying, oil-water separation, water treatment, biology, medicine, and energy fields.
Need to check novelty before this filing date? Find Prior Art

Description

Detailed Description of the Invention

[0001] [Technical field] The present invention relates to the field of polymeric materials, in particular to the field of polymeric membrane materials, especially to superwetting surfaces and methods for their preparation and applications.

[0002] [Background technology] The wettability of the surface of a solid material is usually determined by the chemical properties and microstructure of the solid surface. Polymeric surfaces with superwetting properties find important applications in liquid separation, self-cleaning, anti-fogging, liquid transport, functional polymer films, printing and bonding, etc.

[0003] At present, many researchers have conducted in-depth research on the surface modification of polymers, but the research on superwetting materials mainly obtains superhydrophobic materials. There are few reports on superhydrophilic materials. Obviously, superhydrophilic polymers are more difficult to prepare. The polymer surface obtained by traditional grafting methods (ATRP, corona, plasma treatment, ultraviolet light, etc.) can only be a hydrophilic surface, but cannot be a superhydrophilic surface.

[0004] Superamphiphilic surfaces are more difficult to prepare than superhydrophilic and superoleophilic surfaces, and superamphiphilic surfaces require that both water and oil can penetrate the surface of the material. In 1997, Wang first reported on amphiphilic materials (Wang, R.; Hashimoto, K.; Fujishima, A.; Chikuni, M.; Kojima, E.; Kitamura, A.; Shimohigoshi, M.; Watanabe, T., Light-induced amphiphilic surfaces, Nature 1997, 388(6641), 431-432), in which amphiphilic surfaces were prepared on solid substrates by inducing titania using ultraviolet light, and the surfaces had antifouling capabilities. After that, various superwetting polymer surfaces were prepared using layer-by-layer assembly, electrospinning, etching, plasma treatment, dip coating, phase separation and template methods. However, the superwetting polymer surface prepared by the above method must be composited with inorganic particles, and the brittleness of solid particles in flexible articles limits the application of the material. Therefore, so far, it is still not possible to prepare a superamphiphilic polymer surface without using inorganic particles by existing methods.

[0005] As an emerging high-efficiency separation technology, membrane technology is an industrialized high-efficiency and energy-saving separation method, which has been developing rapidly in recent years. In the application of membrane technology, membrane materials are the basis and core of the development and application of membrane technology. The properties of membrane materials directly affect the separation performance of the membrane, so the preparation process of membrane materials has always been a hotspot for researchers. At present, two types of membrane materials are widely used: polymer and inorganic materials. Among them, the preparation methods of polymer microporous membranes mainly include phase inversion method, stretching method, leaching method, sintering method, nuclear track method, etc. In the early 1980s, Castro filed a patent application, in which a thermally induced phase separation (abbreviated as TIPS) method was proposed, which belongs to the thermogel phase inversion membrane preparation method. The polymer and diluent, which can only be miscible at a higher temperature, were first heated to melt, and then the solution was cast or extruded into a film, which was then cooled. When the temperature of the solution drops below a certain point, the polymer chains in the solution interact to form a gel structure, and eventually phase separation leads to the formation of pores; the separated gel can be immersed in an extract to remove the diluent, thereby forming a porous membrane.

[0006] Polypropylene has characteristics such as high melting point, low density, high strength, and has advantages such as excellent corrosion resistance, chemical stability, and heat resistance, making it extremely advantageous as a starting material for preparing membrane materials. Since polypropylene does not contain polar groups on its surface, its surface energy is very low; and its critical surface tension is 31-34×10 -5N / cm, and therefore it is oleophilic. When polypropylene is prepared into a microporous membrane, the microporous membrane will show stronger oleophilicity, so that the microporous membrane will require higher pressure for water penetration, thereby resulting in high power consumption and low membrane flux. In use, the hydrophobicity of the membrane easily causes the adsorption of organic matter and colloids, such as protein adsorption, on the surface of the membrane and in the pores of the membrane, thereby causing membrane fouling. Pressurization or frequent cleaning is essential for the membrane separation process to proceed normally, which increases the operating energy consumption and cleaning costs, and limits the further widespread application of polypropylene microporous membranes. Such hydrophilic modification of membranes is an important method for improving the water flux of the membrane and the fouling resistance of the membrane, and it has also become one of the current hot spots of research on membranes. In addition, although polypropylene is oleophilic, its oleophilicity is still insufficient. For example, in polypropylene syringes, silicone oil must still be added to increase its oleophilicity. Lipophilic separation membranes also have potential applications in fields such as gas separation. Nevertheless, polypropylene porous membranes with amphiphilic functions have rarely been reported.

[0007] At present, the methods of membrane material modification are mainly divided into physical and chemical methods. Physical methods include surfactant modification, surface coating modification, membrane material blend modification, etc. Chemical methods include plasma modification, ultraviolet radiation grafting, high-energy radiation grafting, introduction of polar groups by other chemical reactions, etc. For example, Chinese patent application publication CN105195031A discloses a method of hydrophilic modification of separation membrane, including mixing a hydrophilic prepolymer and an initiator with a membrane-forming polymer, and then carrying out crosslinking by ultraviolet radiation; and the hydrophilic modification method in Chinese patent CN1299810C (published as CN1539550A) includes precoating a monomer on the surface of a polypropylene separation membrane and carrying out grafting using plasma irradiation. The above methods use complicated equipment and can hardly achieve a uniform effect on the treatment of porous membranes, and are therefore not conducive to industrial application.

[0008] Among these methods of polypropylene film modification, blend modification is a commonly used method. The blend modification method is simple and easy to control, and can simultaneously retain the respective characteristics of multiple polymers, and obvious modification effects can be achieved. In blend modification, water-soluble polymers and nanomaterials are two commonly used additives. Water-soluble polymers such as polyvinylpyrrolidone and polyethylene glycol can significantly increase the membrane flux, but the membrane has poor pressure resistance. Chinese Patent Application Publication CN103768958A provides a method for blending hydrophilic polymers with polyolefin molecular membranes, in which polyolefins are melt-blended with compatibilizers and hydrophilic polymers, and then heat-induced phase separation is carried out to prepare hydrophilic porous membranes. The membranes prepared by nanomaterials have high flux and good pressure resistance, but it is difficult to uniformly disperse nanoparticles in the membrane-forming liquid, which causes a cumbersome membrane preparation process and is unsuitable for industrial production. In Chinese patent application publication CN104548950A, inorganic nanoparticles treated with coupling agents and diluents are added to polypropylene resin for melt blending, and thermally induced phase separation method is adopted to prepare polypropylene hollow fiber separation membranes enhanced by inorganic nanoparticles. Plasma modification, UV irradiation grafting and other modification methods have serious hydrophilic decay with increasing implementation time; or require more complicated chemical reactions, which makes industrialization difficult.

[0009] DISCLOSURE OF THEINVENTION In view of the prior art, it is an object of the present invention to provide a novel superwetting surface that is at least superhydrophilic, has durable and stable superwetting properties, and does not have the disadvantages of the hydrophilic and / or oleophilic surfaces of the prior art.

[0010] Another object of the present invention is to provide a method for preparing such a superwetting surface, by which the superwetting surface can be easily prepared, and the method can be easily industrialized.

[0011] Said object is achieved by the superwetting polypropylene surface and the method for preparing same according to the present invention.

[0012] According to the present invention, it has been unexpectedly found that a superhydrophilic surface can be obtained by grafting a micro-nanostructured polypropylene surface with hydrophilic monomers such as organic acids and organic acid derivatives, vinyl silanes, etc. under microwave irradiation without adding an initiator and optionally by further salification; further grafting with oleophilic monomers such as vinyl silicone oil and styrene can also be carried out, thereby further improving the oleophilicity of the superhydrophilic surface or even achieving a superamphiphilic surface.

[0013] Thus, according to a first aspect of the present invention, there is provided a superwetting surface which is a polypropylene surface having micro-nanostructures and grafted with hydrophilic side groups, wherein said superwetting surface is at least superhydrophilic and wherein said superwetting surface does not contain residues of initiators.

[0014] As used herein, the term "surface" refers to the interface between a solid and air.

[0015] The surface according to the present invention is a superwetting surface. The term "superwetting" as used herein refers to the properties of superhydrophilic, superoleophilic, or superamphiphilic (both superhydrophilic and superoleophilic). The term "superhydrophilic" as used herein means that the surface has a water contact angle of 10° or less, preferably 5° or less, more preferably 1° or less, and most preferably about 0° or less, and in particular the above angle is reached within about 0.5 seconds. The term "superoleophilic" as used herein means that the surface has an oil contact angle of 10° or less, preferably 5° or less, more preferably 1° or less, and most preferably about 0° or less, and in particular the above angle is reached within about 0.5 seconds. The contact angle is measured using a contact angle tester in a dynamic contact angle measurement mode using a water drop or an oil drop (e.g., a drop of white oil or peanut oil).

[0016] The water contact angle of the superwetting surface of the present invention can reach 10° or less, preferably 8° or less, more preferably 5° or less, even more preferably 1° or less, and most preferably about 0°, and in particular reach said angle within about 0.5 seconds.

[0017] The superwetting surfaces of the present invention may be attached to a substrate or may be free-standing, free-standing products.

[0018] The superwetting surface of the present invention is prepared by grafting reaction under microwave irradiation without the addition of an initiator, so that the superwetting surface of the present invention does not contain any initiator residues. As used herein, the term "initiator" refers to substances such as free radical initiators commonly used in the art to initiate polymerization reactions (including grafting reactions) of monomers, including peroxide initiators such as organic peroxide initiators (e.g., dicumyl peroxide) and inorganic peroxide initiators; as well as azo initiators and redox initiators; as well as photoinitiators (or photosensitizers) such as, for example, benzophenone.

[0019] The superwetting surface according to the present invention is a polypropylene surface having micro-nanostructures and grafted with hydrophilic side groups. As used herein, the term "micro-nanostructures" refers to functional structures having feature sizes on the micron or nanoscale and arranged in a specific manner. The functional structures include pore-like structures or structures having other shapes; typically, the feature sizes of micro-nanostructures range from 1 nm to 100 μm. The feature size refers to the average size of the features of the micro-nanostructures.

[0020] The polypropylene surface as the graft base having micro-nano structure can be various polypropylene surfaces having micro-nano structure, and can be prepared by existing preparation methods in the prior art. The feature size of the micro-nano structure of the polypropylene surface is 1 nm to 100 μm. For example, various polypropylene microporous surfaces, preferably polypropylene microporous planes prepared by thermally induced phase separation process, can be used. Existing techniques such as photolithography, femtosecond laser processing technique, plasma etching technique, electrospinning method, nanoimprinting, nanocasting and ultra-precision micromilling technique can also be used to achieve the processing of the micro-nano structure of the polypropylene surface. Specifically, for example, a mold having a micro-nano structure on the surface is used to extrude the micro-nano structure on the polypropylene surface. Alternatively, electric arc and other methods are used to prepare the micro-nano structure on the polypropylene surface, etc.

[0021] The micro-nanostructured polypropylene surface as a graft base can be a free-standing article or can be present on a substrate, which may be composed primarily of polypropylene, for example a film, sheet, plate, or molded article.

[0022] In one embodiment, the polypropylene surface having micro-nano structure as the graft base can be a polypropylene porous membrane, a polypropylene flat membrane or a polypropylene hollow fiber microporous membrane.

[0023] The average pore size of the polypropylene porous membrane may be less than 100 μm, preferably 10 nm to 80 μm, and the porosity of the polypropylene porous membrane may be 50 to 90%, preferably 60 to 80%. The average pore size is determined by observing the microporous surface using a scanning electron microscope, statistically analyzing the pore size data, and plotting a pore size distribution diagram. The porosity is measured using mercury intrusion porosimetry (MIP).

[0024] As used herein, the term "polypropylene" includes homopolymers and copolymers of propylene and mixtures thereof.

[0025] The grafted hydrophilic side groups of the present invention may comprise units formed from hydrophilic monomers, for example, units formed from one or more monomers containing a heteroatom selected from the group consisting of oxygen, sulfur, nitrogen, silicon, and halogens, and combinations or substitutents thereof, and containing a carbon-carbon double bond.

[0026] The hydrophilic side group is a monomeric side group that contains a heteroatom, preferably selected from the group consisting of oxygen, sulfur, nitrogen, silicon, and halogen, and combinations thereof, or substituents thereof, and contains a carbon-carbon double bond. The monomer for the hydrophilic side group is preferably at least one of an organic acid, a derivative of an organic acid, and a vinyl silane. The derivative of an organic acid may include at least one of an anhydride, an ester, and a salt of an organic acid. The organic acid includes, but is not limited to, a carboxylic acid, a sulfonic acid, a sulfinic acid, a thiocarboxylic acid (RCOSH), and the like.

[0027] Monomers for hydrophilic side groups further preferably include organic acids and derivatives of organic acids selected from the group consisting of maleic anhydride, derivatives of maleic anhydride, (meth)acrylic acid, derivatives of (meth)acrylic acid (e.g., glycidyl methacrylate), vinyl acetate, alkenylsulfonic acids and derivatives thereof (e.g., 2-acrylamido-2-methylpropanesulfonic acid, propenylsulfonic acid, vinylbenzenesulfonic acid, vinylsulfonic acid, etc.), vinylbenzoic acid, itaconic acid, oleic acid, arachidonic acid, and combinations thereof, and salt forms thereof; most preferably maleic anhydride, derivatives of maleic anhydride, (meth)acrylic acid, derivatives of (meth)acrylic acid, and combinations thereof, and salt forms thereof; even more preferably maleic anhydride and salt forms thereof.

[0028] The vinyl silane may be one or more of the compounds represented by formula (1): CH2=CH-(CH2) n SiX3 formula (1) In the formula, n=0 to 3, and each X may be the same or different and independently represents a chloro group, a methoxy group, an ethoxy group, or an acetoxy group.

[0029] The vinyl silane is preferably at least one of vinyl trimethoxy silane and vinyl triethoxy silane.

[0030] Preferably, the hydrophilic side groups comprise or consist of units formed from the salt of an organic acid.

[0031] In a preferred embodiment, the polypropylene surface can be simultaneously grafted with lipophilic side groups to further improve the lipophilicity of the surface. Preferably, after modification, the oil contact angle of the superwetting surface can reach less than 90°, preferably 10° or less, more preferably 5° or less, even more preferably 1° or less, and most preferably about 0° or less, and preferably reaches said angle within about 0.5 seconds.

[0032] The lipophilic side groups may include units formed from lipophilic monomers, preferably including at least one of vinyl silicone oil and styrene, and the lipophilic side groups are preferably selected from the group consisting of vinyl silicone oil side groups, styrene side groups, and combinations thereof.

[0033] Vinyl silicone oil generally refers to polysiloxanes with vinyl groups, which are liquid at room temperature and mainly refer to linear polydimethylsiloxanes with vinyl groups at the middle segment or two ends. Vinyl silicone oil can be used as a macromonomer.

[0034] The vinyl silicone oil may be selected from the group consisting of vinyl-terminated silicone oils, high vinyl silicone oils, and combinations thereof, and may be preferably at least one of methyl vinyl silicone oil, vinyl hydrogen-containing silicone oil, and divinyl silicone oil.

[0035] The water contact angle of the superwetting surface according to the present invention is significantly smaller than that of the polypropylene surface before the modification treatment. According to the present invention, after grafting the polypropylene surface having micro-nano structure with hydrophilic side groups, the resulting superwetting surface can achieve superhydrophilic effect. At the same time, the polypropylene surface can be further grafted with an oleophilic monomer for oleophilic modification, which further improves the oleophilicity of the superhydrophilic surface, and improves the oleophilicity compared with both the unmodified polypropylene surface and the polypropylene surface only with hydrophilic modification.

[0036] In the case of polypropylene porous membrane, polypropylene flat membrane or polypropylene hollow fiber microporous membrane, after grafting hydrophilic side groups according to the present invention, the membrane can achieve superhydrophilic effect, while the water flux is also greatly increased. The hydrophilically modified membrane can be further grafted with oleophilic monomers such as vinyl silicone oil, so that the oleophilicity of the membrane is also further improved, and its oil flux is increased compared with both unmodified membrane and only hydrophilically modified membrane.

[0037] According to a second aspect of the invention, the invention provides a method for preparing a superwetting surface according to the invention, comprising a step of subjecting a monomer for forming a side group and a polypropylene surface as a graft base, having a micro-nano structure, to a grafting reaction by microwave irradiation in the absence of an initiator and optionally with the addition of an inorganic microwave absorbing medium. During the grafting reaction, no auxiliary grafting monomer may be used.

[0038] As used herein, the term "microwave" refers to electromagnetic waves having a frequency between 300 MHz and 300 GHz.

[0039] In the method according to the invention, a component comprising monomers for hydrophilic side groups, or a component comprising monomers for hydrophilic side groups and monomers for lipophilic side groups, and a polypropylene surface may be subjected to a grafting reaction using microwave irradiation without the addition of a graft initiator to obtain a superwetting surface.

[0040] If the component does not contain a monomer for a lipophilic side group, then optionally and preferably an inorganic microwave absorbing medium is added; if the component contains a monomer for a lipophilic side group, then an inorganic microwave absorbing medium is added.

[0041] When the monomer for the hydrophilic side group is at least one of an organic acid or an anhydride or an ester thereof, the method may further comprise a step of reacting the product obtained after the grafting reaction with a base (i.e. a so-called salification step).

[0042] In the preparation method of the present invention, the microwave-induced grafting reaction may include only the microwave-induced grafting reaction of the hydrophilic side groups; or it may include both the microwave-induced grafting reaction of the lipophilic side groups and the microwave-induced grafting reaction of the hydrophilic side groups, and the microwave-induced grafting reactions of the two types of side groups may occur simultaneously or sequentially, and the order is not limited.

[0043] The salification step is an optional step. When the polypropylene surface is grafted with at least one side group of an organic acid or its anhydride or its ester, such a salification step can be carried out, but it is not limited whether it is carried out before, after or during the microwave irradiation grafting reaction of the lipophilic side group, i.e., for salification of said hydrophilic side group, it is possible to add a base during microwave irradiation grafting of the lipophilic side group on the grafted polypropylene surface having a monomer for the hydrophilic side group, which is at least one of an organic acid or its anhydride or ester.

[0044] The preparation method of the present invention may specifically include any one of the following approaches: 1) contacting and mixing a polypropylene surface with a monomer and / or a solution of monomers for hydrophilic side groups in a solvent, where an inorganic microwave absorbing medium is optionally added; then subjecting the resulting mixture to microwave irradiation grafting without the addition of a graft initiator; said mixture optionally further comprising a monomer and / or a solution of monomers for lipophilic side groups in a solvent, and an inorganic microwave absorbing medium; 2) contacting and mixing a polypropylene surface with a monomer and / or a solution of monomer for hydrophilic side groups in a solvent, optionally with the addition of an inorganic microwave absorbing medium; then subjecting the resulting mixture to microwave irradiation grafting without the addition of a graft initiator; then mixing the resulting grafted product with a monomer and / or a solution of monomer for lipophilic side groups in a solvent, and an inorganic microwave absorbing medium, and microwave irradiation grafting without the addition of a graft initiator; 3) contacting and mixing a polypropylene surface with monomers and / or a solution of monomers for lipophilic side groups in a solvent, and an inorganic microwave absorbing medium, then subjecting the resulting mixture to microwave irradiation grafting without the addition of a graft initiator, and then mixing the resulting grafted product with monomers and / or a solution of monomers for hydrophilic side groups in a solvent, optionally with the addition of an inorganic microwave absorbing medium, and microwave irradiation grafting without the addition of a graft initiator; 4) Based on any one of the above three approaches, when the monomer for the hydrophilic side group is at least one of an organic acid or an anhydride or ester thereof, it further comprises a step of contacting and mixing the polypropylene surface grafted with at least one side group of an organic acid or an anhydride or ester thereof with a base and / or an aqueous solution of said base (the so-called salification step).

[0045] Since the preparation method of the present invention does not add either initiator or graft initiator, the super-wetting surface of the present invention obtained by the preparation method does not contain any initiator residue. Initiator refers to a substance used in the art to initiate the polymerization reaction (including graft reaction) of monomers, such as free radical initiators including peroxide initiators, azo initiators, redox initiators, etc., or photoinitiators (or photosensitizers) such as, for example, benzophenone. Peroxide initiators can be divided into organic peroxide initiators (e.g., dicumyl peroxide) and inorganic peroxide initiators. Initiators refer in particular to various initiators used to graft functional monomers onto polypropylene, such as dicumyl peroxide. In the prior art grafting method, in order to graft polypropylene with monomers, the tertiary carbon of polypropylene is dehydrogenated by the initiator, but in reality, the initiator not only dehydrogenates but can also significantly cause β-chain scission reaction in polypropylene, i.e., the reaction is too violent to be controlled, thus affecting the mechanical properties of the grafted polypropylene. The preparation method of the present invention can graft side groups such as organic acid, organic acid derivatives, vinyl silane, vinyl silicone oil and styrene onto the surface of polypropylene without adding initiator. Therefore, the super-wetting surface obtained by the present invention does not contain initiator residues, thus ensuring that the mechanical properties of the polypropylene surface are not adversely affected.

[0046] The monomers for hydrophilic side groups used in the preparation method of the present invention may be various hydrophilic monomers, in particular those mentioned above. The amount of monomers for hydrophilic side groups may be 0.1-10% by weight, preferably 1-8% by weight, based on the amount of polypropylene surface.

[0047] In this specification, when the polypropylene surface as a graft base is an independent article, if the thickness of the article is 1 mm or less, the amount of the polypropylene surface is calculated according to the total weight of the article; if the thickness of the article is more than 1 mm, the amount of the polypropylene surface is calculated according to the weight of the article with a thickness of 1 mm. When the polypropylene surface as a graft base is present in a substrate, the amount of the polypropylene surface is calculated according to the weight of the entire substrate, including the polypropylene surface from the surface in contact with air in the direction toward the substrate interior to the position of 1 mm thickness; if the thickness of the entire substrate including the polypropylene surface is 1 mm or less, the amount is calculated according to the total weight of the entire substrate including the polypropylene surface.

[0048] The monomer for hydrophilic side groups can be directly contacted and mixed with the polypropylene surface or the polypropylene surface grafted with lipophilic monomers, or for better mixing effect, a solution of the monomer for hydrophilic side groups in one or more solvents can be used for mixing. The amount of solvent is only required to the extent that it can dissolve the monomer to form a solution, preferably in the solution of the monomer for hydrophilic side groups, the weight ratio of monomer to solvent is (0.1-100):100, preferably (0.5-50):100, more preferably (1-30):100. Preferably, the monomer solution is used in such an amount that it can completely cover the polypropylene surface, facilitating sufficient contact and mixing of the two.

[0049] The solvent used to dissolve the monomers for the hydrophilic side groups can be at least one selected from the group consisting of water and organic solvents; preferably, it comprises at least one of alcohols, ketones, esters and water, more preferably, it is acetone or ethanol.

[0050] The monomers for the lipophilic side groups used in the preparation method of the present invention may be various lipophilic monomers, in particular those mentioned above. The amount of the lipophilic side group monomer may be 0.1-30% by weight, preferably 1-20% by weight, based on the amount of polypropylene surface.

[0051] The monomer of the lipophilic side group may be directly contacted and mixed with the polypropylene surface or the polypropylene surface grafted with the hydrophilic monomer, or for better mixing effect, a solution of the monomer of the lipophilic side group in one or more solvents may be used for mixing. The amount of solvent is only required to the extent that it can dissolve the monomer to form a solution, preferably, the weight ratio of the monomer to the solvent for the lipophilic side group may be (0.1-100):100, preferably (0.5-50):100, more preferably (1-30):100. Preferably, the monomer solution is used in such an amount that it can completely cover the polypropylene surface, facilitating sufficient contact and mixing of the two.

[0052] The solvent used to dissolve the monomer for the lipophilic side group can be at least one selected from the group consisting of water and organic solvents; preferably, it comprises at least one of alcohols, ketones, esters and water, more preferably, it is acetone or ethanol.

[0053] In the preparation method of the present invention, when the polypropylene surface is grafted only with hydrophilic side groups, it is not necessary to add an inorganic microwave absorbing medium to the mixture of monomer and polypropylene surface, but it is preferable to add an inorganic microwave absorbing medium to improve the grafting efficiency.When the polypropylene surface needs to be grafted with lipophilic side groups, generally, the rising temperature of the monomer for the lipophilic side groups under microwaves does not exceed 200°C, and the grafting reaction cannot proceed sufficiently, so it is necessary to add an inorganic microwave absorbing medium to promote the grafting reaction under microwaves.

[0054] As the inorganic microwave absorbing medium, various inorganic substances capable of absorbing microwaves may be used, and preferably include at least one of metal hydroxides, metal salts, metal oxides, graphite materials, ferroelectric materials, chalcopyrite, and electrolytic stones.

[0055] The metal hydroxide may be at least one of potassium hydroxide, barium hydroxide, sodium hydroxide, lithium hydroxide, strontium hydroxide, calcium hydroxide, iron hydroxide, ferrous hydroxide, zinc hydroxide, magnesium hydroxide, cobalt hydroxide, gold hydroxide, aluminum hydroxide, copper hydroxide, beryllium hydroxide, and rare earth hydroxide; the metal salt may be at least one of ammonium nitrate, potassium nitrate, sodium nitrate, barium nitrate, calcium nitrate, magnesium nitrate, aluminum nitrate, manganese nitrate, zinc nitrate, ferric nitrate, ferrous nitrate, copper nitrate, silver nitrate, ammonium chloride, potassium chloride, sodium chloride, barium chloride, calcium chloride, magnesium chloride, aluminum chloride, manganese chloride, zinc chloride, ferric chloride, ferrous chloride, copper chloride, ammonium sulfate, sulfur, the metal oxide may be at least one selected from the group consisting of ferric oxide, potassium sulfate, sodium sulfate, calcium sulfate, magnesium sulfate, aluminum sulfate, manganese sulfate, zinc sulfate, ferrous sulfate, ferrous sulfate, copper sulfate, silver sulfate, ammonium carbonate, potassium carbonate, sodium carbonate, magnesium carbonate, calcium carbonate, barium carbonate, potassium dihydrogen phosphate, barium titanate, strontium titanate, and calcium copper titanate; the metal oxide may be at least one selected from the group consisting of ferric oxide and ferric oxide; the graphite material may be at least one selected from the group consisting of carbon black, graphite powder, graphene, a reduction product of graphene oxide (the reducing agent is, for example, ascorbic acid), carbon nanotubes, and activated carbon.

[0056] The amount of inorganic microwave absorbing medium in one use can be 0.1-10% by weight of the amount of polypropylene surface, preferably 1-8% by weight. The amount of inorganic microwave absorbing medium in one use means the amount added for one microwave irradiation, when the inorganic microwave absorbing medium is added, in which the preparation method of the present invention may include one or more microwave irradiations.

[0057] The inorganic microwave absorbing medium can be directly added to the polypropylene surface or the grafted polypropylene surface for contacting and mixing, or for better mixing effect, the inorganic microwave absorbing medium solution or dispersion obtained by dissolving or dispersing in one or more solvents is added for contacting and mixing. In order to better disperse and mix the inorganic microwave absorbing medium on the (grafted) polypropylene surface, preferably, the mixing of the inorganic microwave absorbing medium with the (grafted) polypropylene surface and the mixing with other components such as monomers are carried out stepwise, i.e., the (grafted) polypropylene surface can be mixed with the monomer components separately and dried, and then the dried mixture can be mixed with at least one of the inorganic microwave absorbing medium or its solution or dispersion.

[0058] The amount of solvent used to dissolve or disperse the microwave absorbing medium is only required to the extent that the inorganic microwave absorbing medium can be dissolved to form an inorganic microwave absorbing medium solution, or the inorganic microwave absorbing medium can be sufficiently and uniformly dispersed to form a dispersion. In the inorganic microwave absorbing medium solution or dispersion, the weight ratio of inorganic microwave absorbing medium to solvent may preferably be in the range of (0.1-100):100, more preferably in the range of (0.5-50):100, and most preferably in the range of (1-30):100.

[0059] The inorganic microwave absorbing medium solution or dispersion is preferably used in an amount such that it can completely cover the mixture of starting materials including the (grafted) polypropylene surface to facilitate thorough contact, mixing and reaction of the starting materials.

[0060] The solvent in the inorganic microwave absorbing medium solution or dispersion is at least one selected from the group consisting of water and organic solvents; preferably including at least one of alcohols, ketones, esters, and water, more preferably alcohols and water.

[0061] In order to ensure that the inorganic microwave absorbing medium can be sufficiently dispersed and form a stable dispersion with the solvent, a surfactant commonly used in the prior art can be added to the dispersion of the inorganic microwave absorbing medium. In general, surfactants such as polyoxyethylene type and polyol type can be used, and the amount used can usually be 0.1 to 100% by weight of the inorganic microwave absorbing medium.

[0062] The base used in the salification step may be selected from bases capable of salifying any one of the organic acid side groups grafted onto the polypropylene surface, its acid anhydride side groups, and its ester side groups, and is preferably a hydroxide.

[0063] The hydroxide is preferably at least one of a metal hydroxide and aqueous ammonia; wherein the metal hydroxide is preferably one or more of sodium hydroxide, potassium hydroxide, barium hydroxide, lithium hydroxide, strontium hydroxide, calcium hydroxide, iron hydroxide, ferrous hydroxide, zinc hydroxide, magnesium hydroxide, cobalt hydroxide, gold hydroxide, aluminum hydroxide, copper hydroxide, beryllium hydroxide and rare earth hydroxide, preferably one or more of sodium hydroxide, potassium hydroxide, barium hydroxide, lithium hydroxide, strontium hydroxide and calcium hydroxide.

[0064] The amount of base (eg, hydroxide) can be 0.1 to 10% by weight based on the amount of polypropylene surface; preferably 1 to 8% by weight.

[0065] To contact and mix the base with the grafted polypropylene surface, the base may be added directly or, to facilitate thorough mixing, the base is preferably used in the form of an aqueous solution. The amount of water used to dissolve the base is also only required to the extent that the base can be dissolved to form an aqueous solution. In the aqueous solution of the base, the weight ratio of base to water may preferably be (0.1-100):100, more preferably (0.5-50):100, and most preferably (1-30):100. The amount of the aqueous solution of the base is preferably such that the grafted polypropylene surface can be completely covered, facilitating thorough contact, mixing and reaction of the two.

[0066] The base and / or the aqueous solution of the base can be mixed thoroughly with the grafted polypropylene surface and react with it at the same time, which is a general acid-base reaction, and the reaction time is not particularly required as long as the reaction continues until it is sufficient. Generally, after the addition of the base and / or the aqueous solution is completed, further contact and mixing is carried out simultaneously with the reaction for a while, for example, perhaps within 30 minutes, preferably within 5 to 10 minutes. Both the reaction temperature and pressure are not limited, and can generally be normal temperature and pressure.

[0067] The microwave irradiation process in the preparation method of the present invention can be carried out in various microwave reactors. As long as it can achieve a suitable graft modification effect on the polypropylene surface and thus achieve the super-wetting properties according to the present invention, the microwave irradiation process can be carried out using any suitable irradiation power and can continue for any suitable period of time. For example, the irradiation power may be 100W to 2000W, preferably 500 to 1000W, more preferably 600W to 800W, and the irradiation time may be 1 second to 120 minutes, preferably 1 minute to 30 minutes, more preferably 3 minutes to 10 minutes.

[0068] The microwave irradiation is preferably carried out under an inert atmosphere, which may be one or more of an inert gas, preferably nitrogen, helium and argon, more preferably nitrogen.

[0069] In the preparation method of the present invention, the mixing is preferably carried out under vacuum conditions. Mixing includes contact mixing of a monomer and / or a solution thereof for hydrophilic side groups with the (grafted) polypropylene surface, contact mixing of a monomer and / or a solution thereof for lipophilic side groups with the (grafted) polypropylene surface, contact mixing of a grafted polypropylene surface with a base and / or an aqueous solution of a base, etc.

[0070] For the polypropylene surface itself having a micro-nano structure, such as microporous, the vacuum is favorable for more thorough contact mixing with the grafting monomer and / or base, as well as other components; the vacuum promotes the grafting monomer and / or base, as well as other components, to enter the micro-nano structure of the polypropylene surface, which is more favorable for the reaction to proceed.

[0071] In the preparation method of the present invention, the contact mixing can be carried out by various mixing methods and devices, and the mixing conditions are also general conditions as long as various materials can be mixed sufficiently and uniformly; for example, starting materials of components containing monomers other than polypropylene surface, or their solutions, dispersions, etc. can be coated, dropped, infiltrated, or covered on the polypropylene surface to achieve contact mixing.

[0072] Preferably, the mixture of ingredients comprising the monomer and the (grafted) polypropylene surface is subjected to a drying treatment prior to microwave irradiation.

[0073] Preferably, the microwave grafted product can be washed with a solvent to remove unreacted monomers or / and inorganic microwave absorbing medium that does not participate in the reaction, and is preferably subjected to a further drying treatment after washing.

[0074] The washing of the product after microwave irradiation is not particularly limited as long as it can remove residual monomers or inorganic microwave absorbing media. A general washing method can be used. For example, after microwave irradiation, a volume of solvent exceeding the polypropylene surface is immediately used to immerse the polypropylene surface at high temperature for a certain period of time (e.g., 5 to 15 minutes), and then a filtration device is used to remove excess water; by repeating the immersion and filtration multiple times (e.g., 2 to 6 times), a super-wet surface without impurities can be obtained.

[0075] The product of the salification step (i.e., the product after reaction of the graft reaction product with a base) can preferably be washed with a solvent to remove any base that has not reacted with the grafted polypropylene surface, and is preferably further dried after washing.

[0076] The washing of the product after salification is not particularly limited as long as the residual base can be removed, and a general washing method can be used. For example, after the salification reaction, a solvent with a volume exceeding the volume of the grafted polypropylene surface is immediately used for immersion for a certain period of time (for example, 5 to 15 minutes), and then a filtration device is used to remove excess water; the immersion and filtration are repeated multiple times (for example, 2 to 6 times) to obtain an amphiphilic propylene surface free of impurities.

[0077] The washing solvent may be at least one selected from the group consisting of water and organic solvents; preferably it comprises at least one of alcohols, ketones, esters and water, more preferably alcohols and water.

[0078] Various conventional drying methods can be used as the drying treatment, including, but not limited to, air blast drying, room temperature drying, etc. A preferred drying temperature is one at which polypropylene does not melt, e.g., 160° C. or less.

[0079] In a third aspect of the invention, the invention provides an article consisting of or comprising the superwetting surface of the invention. The article can be a film, sheet, plate or molded article, such as a polypropylene porous membrane, a polypropylene flat membrane or a polypropylene hollow fiber microporous membrane, a bonded plastic article, a sprayed outer packaging of a food bag, a sprayed automobile bumper, etc. The article can be composed primarily of polypropylene.

[0080] In a fourth aspect of the invention, the invention provides applications of the superwetting surface according to the invention or articles comprising said superwetting surface in the fields of bonding (such as bonding of plastic articles) and spraying (such as spraying outer packaging of food bags and spraying of car bumpers) or in the fields of oil-water separation, water treatment, biology, medicine and energy. Similarly, the invention provides methods of bonding, spraying, oil-water separation or water treatment using the superwetting surface or article according to the invention, such as methods for preparing bonded plastic articles, sprayed outer packaging of food bags and sprayed car bumpers.

[0081] For example, the amphiphilic polypropylene porous membrane obtained by the present invention can be used in the fields of oil-water separation, water treatment, biology, medicine, energy, etc.

[0082] The superwetting surface of the present invention can achieve superhydrophilicity or even amphiphilicity. The present invention obtains a superwetting surface by subjecting hydrophilic monomers, such as organic acids and derivatives of organic acids, and a polypropylene surface to a grafting reaction using microwave irradiation without the addition of an initiator, or by including further chlorination, and furthermore, due to the oleophilicity of the polypropylene itself, an oleophilic and superhydrophilic surface is already formed at this point; optionally, a further grafting reaction with an oleophilic monomer, such as vinyl silicone oil, is carried out using microwave irradiation without the addition of an initiator, thereby further improving the oleophilicity of the superwetting surface, or further obtaining a superamphiphilic surface. Polypropylene is microwave transparent in a microwave environment (it absorbs little or no microwaves under microwave irradiation, and therefore does not generate heat under microwave irradiation). Monomers such as organic acids and organic acid derivatives used as graft monomers absorb microwaves under microwave conditions, achieve a temperature rise of up to 200°C or more, and generate free radicals; at the same time, the high temperature also initiates the nearby polypropylene molecular chains to generate free radicals, and thus a sufficient grafting reaction with polypropylene will occur, thereby obtaining a grafted polypropylene surface. At the same time, such microwave grafting reaction without adding initiator can largely avoid the β-chain scission reaction of polypropylene when grafting with adding initiator, thereby not reducing the molecular weight of polypropylene.

[0083] When the polypropylene grafted with a side group of an organic acid or its anhydride or ester is further reacted with a base such as a hydroxide, the grafted polypropylene surface becomes an organic acid salt grafted polypropylene surface, and the hydrophilicity of the polypropylene surface is further improved. For polypropylene porous membranes, polypropylene flat membranes, polypropylene hollow fiber microporous membranes, etc., the water flux is also greatly increased.

[0084] When further lipophilic modification is performed on the superhydrophilic polypropylene surface, lipophilic monomers such as vinyl silicone oil have low polarity and absorb microwaves under microwave irradiation, but on the other hand, the temperature rise cannot reach extremely high temperatures (the temperature in the microwave field rises to less than 200°C), and cannot effectively initiate nearby polypropylene molecular chains to generate free radicals; therefore, it is necessary to add an inorganic microwave absorbing medium to help polypropylene generate free radicals and thereby participate in the grafting reaction with vinyl silicone oil. The inorganic microwave absorbing medium does not react with the polypropylene surface and monomers, and therefore simply serves as a heat source for the grafting reaction and does not affect the properties of the polypropylene surface. For monomers that do not absorb microwaves, the addition of an inorganic microwave absorbing medium can help them to graft onto polypropylene; for monomers that absorb microwaves themselves, such addition can contribute to increasing their grafting efficiency. The present invention utilizes selective heating of microwaves to heat the inorganic microwave absorbing medium, which can be heated under microwaves to a temperature of 200°C or more, approaching the melting point of polypropylene. At said temperature, the chain of polypropylene is not broken, but the tertiary carbon of polypropylene can be dehydrogenated, so that the grafting reaction occurs but does not cause the chain scission reaction. After grafting the oleophilic monomer such as vinyl silicone oil, the oleophilicity of the superhydrophilic polypropylene surface is further improved.

[0085] On the other hand, since the polypropylene surface used in the present invention has a micro-nano structure, the capillary action present in said structure further enhances the hydrophilic and oleophilic properties of the surface.

[0086] The preparation method of the present invention has a simple process and is easy to operate. Such a modification method is suitable for various polypropylene surfaces, adopts simple equipment, requires low cost, and can be easily industrialized. The obtained super-wetting surface has durable and stable super-wetting properties, and has no residual graft monomer, residual base, initiator residue, etc. In the preparation process, the molecular weight of the grafted polypropylene is not reduced. For polypropylene porous membrane, polypropylene flat membrane, polypropylene hollow fiber microporous membrane, etc., the membrane after graft modification has a significantly increased water flux, or has a significantly increased water flux and oil flux.

[0087] [Example] The present invention will now be further described in conjunction with the following examples, but the scope of the present invention is not limited to these examples, and is instead described in the appended claims.

[0088] 1.Measurement method 1) Contact angle test method Using an EASY DROP contact angle tester (measurement range 1-180°, resolution ±0.1°) manufactured by KRUSS (Germany), a dynamic contact angle measurement mode was adopted, and a deionized water droplet or oil droplet (white oil droplet or peanut oil droplet) with a fixed amount of 2 μL was dropped onto the surface to be tested in each measurement, and the calculated initial (within 0.5 seconds) contact angle was taken as the contact angle measurement value of the surface; the same measurement was performed six times to calculate the average value. If the measured value was below the lower measurement limit of the instrument (1°), the data was recorded as 0.

[0089] White oil was purchased from Tianma (Karamay) Petroleum Company, and peanut oil was purchased from Shandong Luhua Group Co., Ltd.

[0090] 2) Method for determining the content of grafted side groups on the surface: The energy spectrum attachment of a Hitachi S4800 scanning electron microscope (Japan) was used to measure the contents of the main elements of the grafted components on the tested surfaces, and the content of the grafts on the surface, which was inversely estimated by the molecular formula of the grafts, was taken as the surface grafting ratio. The content was the surface content (usually the content at a thickness of 1-2 mm from the surface of the object), so the content was higher than the content of the monomer in the starting material.

[0091] 3) Methods for measuring water and oil flux Five test surfaces (e.g., polypropylene porous membranes) were prepared by removing the outer membrane layer using a freezing microtome knife to prepare membrane conjugates. Deionized water, chloroform, and peanut oil were used for filtration for 30 minutes under normal pressure, and the obtained values ​​were the water flux and oil flux of the surface or membrane.

[0092] 4) Method for measuring the average pore diameter and average size of micropores: A scanning electron microscope (S-4800 field emission scanning electron microscope, Hitachi, Japan, magnification: 5000) was used to observe the surfaces of the pores or micropores, calculate the pore size data, and plot the pore size distribution diagram to measure the average pore size and average size of the micropores.

[0093] The porosity was measured using mercury intrusion porosimetry (MIP) with a mercury intrusion porosimeter (Poremaster-33, Quantachrome, USA).

[0094] 2. Starting materials and equipment used in the examples and comparative examples 1) Polypropylene surface sample with micro-nano structure Surface sample 1: A polypropylene flat membrane (average pore size 0.8 μm, porosity 80%) manufactured by Tianjin Motimo Membrane Engineering Technology Co., Ltd. was used, and one side of the membrane was sealed with an epoxy resin adhesive (DP100NS manufactured by 3M). On the other side, the outer membrane layer was removed using a Leica CM3600 cryomicrotome in a liquid nitrogen atmosphere to obtain polypropylene microporous membrane surface sample 1 with an average surface pore size of 0.8 μm.

[0095] Surface sample 2: Polypropylene resin (T30S Qilu Petrochemical, MI=3g / 10min) was injected to obtain a 5cm×5cm thin plate with a thickness of 1mm, and a surface with a microstructure was prepared using an ultra-small ultra-precision micro-milling machine, specifically, milling was performed in the horizontal and vertical directions along the thin plate surface, respectively, to obtain a surface micro-nanostructure with an average upper surface size of 0.5μm.

[0096] Surface sample 3: A 5 cm × 5 cm thin plate with a thickness of 1 mm was obtained by injecting polypropylene resin (T30S manufactured by Qilu Petrochemical, MI = 3 g / 10 min), and a nanoimprint machine was used to prepare a surface with a nanostructure, specifically, surface micro-nanostructures of small depressions and protrusions with an average size of 80 nm were imprinted.

[0097] Surface sample 4: polypropylene porous membrane (manufactured by Tianjin Motimo Membrane Engineering Technology Co., Ltd., specification 1: average pore size 0.8 μm, porosity 80%).

[0098] Surface sample 5: polypropylene porous membrane (manufactured by Tianjin Motimo Membrane Engineering Technology Co., Ltd., specification 2: average pore size 0.22 μm, porosity 45%).

[0099] 2) Maleic anhydride (Xilong Science Co., Ltd.), acrylic acid (Sinopharm Chemical Reagent Co., Ltd.), methacrylic acid (Sinopharm Chemical Reagent Co., Ltd.), 2-acrylamido-2-methylpropanesulfonic acid (Sinopharm Chemical Reagent Co., Ltd.), sodium hydroxide (Xilong Science Co., Ltd.), potassium hydroxide (Xilong Science Co., Ltd.), calcium hydroxide (Xilong Science Co., Ltd.), acetone (Xilong Science Co., Ltd.), sodium chloride (Sinopharm Chemical Reagent Co., Ltd.), vinyl silicone oil (methyl vinyl silicone oil, Shandong Dayi Chemical Co., Ltd., product name: DY-V401, linear type, molecular formula: (CH2=CH)Si(CH3)2O[(CH3)2SiO] n (CH3)2Si(CH=CH2)), vinyl hydrogen-containing silicone oil (Shandong Dayi Chemical Co., Ltd., product name: DY-H202, molecular formula: (CH3)3SiO[(CH3)(H)SiO] n Si(CH3)3), divinyl silicone oil (Shandong Dayi Chemical Co., Ltd., product name: DY-V421, linear type, molecular formula: (CH2=CH)(CH3)2SiO[(CH3)2SiO] m [(CH2=CH)(CH3)SiO] n Si(CH3)2(CH2=CH)), sodium chloride (Sinopharm Chemical Reagent Co., Ltd.), an aqueous solution of graphene oxide (GO) (Nanjing JCNANO Tech Co., Ltd., concentration 1 wt%), ascorbic acid (J&K Co.), vinyltrimethoxysilane (Tokyo Chemical Industry Co., Ltd.), and styrene (Sinopharm Chemical Reagent Co., Ltd.). A variety of other starting materials were commercially available.

[0100] 3) Microwave equipment: SINEO (Sineo) multi-function microwave synthesis extraction equipment, model: UWave-2000.

[0101] Example 1 Based on 100 parts by mass of the polypropylene surface sample (surface sample 1), maleic anhydride (5 parts by mass) was dissolved in acetone (50 parts by mass) to obtain an acetone solution of maleic anhydride; sodium hydroxide (5 parts by mass) was dissolved in deionized water (50 parts by mass) to obtain an aqueous sodium hydroxide solution; the acetone solution of maleic anhydride was added to the polypropylene surface sample under vacuum to thoroughly contact and mix them, and then the mixture was dried (dried in a blast drying oven at 80°C). After drying, the dried mixture of maleic anhydride and polypropylene surface sample was irradiated with microwaves for 5 minutes under nitrogen atmosphere (power 700W); the product after microwave irradiation was immersed in deionized water for 10 minutes, and the deionized water was replaced three times repeatedly to ensure the removal of maleic anhydride monomers that were not involved in the grafting reaction, and then placed in a blast drying oven at 80 ° C to dry, thereby obtaining a dried maleic anhydride grafted polypropylene surface sample; the sodium hydroxide aqueous solution was thoroughly contacted and mixed with the dried maleic anhydride grafted polypropylene surface sample under vacuum; after the addition of the sodium hydroxide aqueous solution was completed, the mixing and reaction was continued for another 5 minutes. After the reaction was completed, the reaction product was washed with deionized water according to the same washing steps as above, and then placed in a blast drying oven at 80 ° C to dry, thereby obtaining a sodium maleate grafted polypropylene surface sample.

[0102] Based on 100 parts by mass of the polypropylene surface sample, vinyl silicone oil (5 parts by mass) was dissolved in ethanol (50 parts by mass) to obtain an ethanol solution of vinyl silicone oil; sodium chloride (5 parts by mass) was dissolved in deionized water (50 parts by mass) to obtain an aqueous sodium chloride solution; the ethanol solution of vinyl silicone oil was added under vacuum to the sodium maleate-grafted polypropylene surface sample obtained above to thoroughly contact and mix them, and then the mixture was dried (dried in a blast drying oven at 80°C); after drying, the dried mixture of vinyl silicone oil and sodium maleate-grafted polypropylene surface sample was The mixture was thoroughly mixed in contact with an aqueous sodium chloride solution, then the mixture was dried (dried in a blast oven at 80°C); the dried mixture was irradiated with microwaves for 5 minutes under nitrogen atmosphere (power 700W); the material after microwave irradiation was immersed in deionized water for 10 minutes, and the deionized water was replaced three times repeatedly to ensure the removal of vinyl silicone monomer and sodium chloride that were not involved in the grafting reaction; the resulting polypropylene surface sample was then dried in a blast oven at 80°C, thereby obtaining a polypropylene superwetting surface sample grafted with sodium maleate side groups and vinyl silicone oil side groups. The water contact angle and oil contact angle as well as the surface grafting rate data of the resulting superwetting surface are shown in Table 1.

[0103] Example 2 Based on 100 parts by mass of the polypropylene surface sample (same as in Example 1), maleic anhydride (5 parts by mass) was dissolved in acetone (50 parts by mass) to obtain an acetone solution of maleic anhydride; sodium hydroxide (5 parts by mass) was dissolved in deionized water (50 parts by mass) to obtain an aqueous sodium hydroxide solution; the acetone solution of maleic anhydride was added to the polypropylene surface sample under vacuum to thoroughly contact and mix them, and then the mixture was dried (dried in a blast drying oven at 80°C). After drying, the dried mixture of maleic anhydride and polypropylene surface sample was irradiated with microwaves under nitrogen atmosphere for 5 minutes (power 700W); the product after microwave irradiation was immersed in deionized water for 10 minutes, and the deionized water was replaced three times repeatedly to ensure the removal of maleic anhydride monomers that were not involved in the grafting reaction, and then placed in a blast drying oven at 80 °C to dry, obtaining a dried maleic anhydride grafted polypropylene surface sample; sodium hydroxide aqueous solution was added to the dried maleic anhydride grafted polypropylene surface sample under vacuum to bring them into contact and mix thoroughly; after the addition of sodium hydroxide aqueous solution was completed, the mixing and reaction was continued for another 5 minutes. After the reaction was completed, the reaction product was washed with deionized water according to the same washing steps as above, and then placed in a blast drying oven at 80 °C to dry, thereby obtaining a polypropylene superwet surface sample grafted with sodium maleate side groups. The water contact angle and oil contact angle as well as the surface grafting rate data of the obtained superwet surface are shown in Table 1.

[0104] Example 3 Based on 100 parts by weight of polypropylene surface sample (same as in Example 1), vinyl silicone oil (9 parts by weight) was dissolved in ethanol (50 parts by weight) to obtain an ethanol solution of vinyl silicone oil; sodium chloride (4 parts by weight) was dissolved in deionized water (50 parts by weight) to obtain an aqueous sodium chloride solution; the ethanol solution of vinyl silicone oil was added to the polypropylene surface sample under vacuum to thoroughly contact and mix them, and then the mixture was dried (dried in a blast drying oven at 80 ° C); after drying, the dried mixture of vinyl silicone oil and polypropylene surface sample was thoroughly contacted and mixed with an aqueous sodium hydroxide solution, and then the mixture was dried (dried in a blast drying oven at 80 ° C); the dried mixture was irradiated with microwaves for 3 minutes under a nitrogen atmosphere (power 1000 W); the material after the microwave irradiation was immersed in deionized water for 10 minutes, and the deionized water was replaced three times repeatedly to ensure the removal of vinyl silicone monomer and sodium chloride that were not involved in the grafting reaction, and then placed in a blast drying oven at 80 ° C to dry, thereby obtaining a polypropylene surface sample grafted with vinyl silicone oil side groups.

[0105] Based on 100 parts by weight of the polypropylene surface sample, acrylic acid (9 parts by weight) was dissolved in acetone (50 parts by weight) to obtain an acetone solution of acrylic acid; potassium hydroxide (6 parts by weight) was dissolved in deionized water (50 parts by weight) to obtain an aqueous potassium hydroxide solution; the acetone solution of acrylic acid was added to the grafted polypropylene surface sample under vacuum to thoroughly contact and mix them, and then the mixture was dried (dried in a blast drying oven at 80°C). After drying, the dried mixture of acrylic acid and grafted polypropylene surface sample was irradiated with microwaves under nitrogen atmosphere for 3 minutes (power 1000W); the product after microwave irradiation was immersed in deionized water for 10 minutes, and the deionized water was replaced three times repeatedly to ensure the removal of acrylic acid monomers that were not involved in the grafting reaction, and then placed in a blast drying oven at 80 °C to dry, obtaining a dried grafted polypropylene surface sample grafted with acrylic acid and vinyl silicone oil; potassium hydroxide aqueous solution was added under vacuum to the dried grafted polypropylene surface sample grafted with acrylic acid and vinyl silicone oil to thoroughly contact and mix them, and further mixing and reaction were continued for 5 minutes after the addition of potassium hydroxide aqueous solution was completed. After the reaction was completed, the reaction product was washed with deionized water according to the same washing steps as above, and then placed in a blast drying oven at 80 °C to dry, thereby obtaining a polypropylene superwet surface sample grafted with potassium acrylate side groups and vinyl silicone oil side groups. The water contact angle and oil contact angle as well as the surface grafting rate data of the obtained superwet surface are shown in Table 1.

[0106] Example 4 Based on 100 parts by mass of the polypropylene surface sample (same as in Example 1), acrylic acid (9 parts by mass) was dissolved in acetone (50 parts by mass) to obtain an acetone solution of acrylic acid; potassium hydroxide (6 parts by mass) was dissolved in deionized water (50 parts by mass) to obtain an aqueous potassium hydroxide solution; the acetone solution of acrylic acid was added to the polypropylene surface sample under vacuum, and they were thoroughly contacted and mixed, and then the mixture was dried (dried in a blast drying oven at 80°C). After drying, the dried mixture of acrylic acid and polypropylene surface sample was irradiated with microwaves for 3 minutes under a nitrogen atmosphere (power 1000W); the product after the microwave irradiation was immersed in deionized water for 10 minutes, and the deionized water was replaced three times repeatedly to ensure the removal of acrylic acid monomers that were not involved in the graft reaction, and then placed in a blast drying oven at 80°C to dry, thereby obtaining a dried acrylic acid-grafted polypropylene surface sample; an aqueous potassium hydroxide solution was added to the dried acrylic acid-grafted polypropylene surface sample under vacuum, and they were thoroughly contacted and mixed; after the addition of the aqueous potassium hydroxide solution was completed, the mixing and reaction were continued for another 5 minutes. After the reaction was completed, the reaction product was washed with deionized water according to the same washing steps as above, and then dried in a blast drying oven at 80°C, thereby obtaining a polypropylene superwetting surface sample grafted with potassium acrylate side groups. The water contact angle and oil contact angle as well as the surface grafting ratio data of the obtained superwetting surface are shown in Table 1.

[0107] Comparative Example 1 A polypropylene surface sample (same as in Example 1) was tested directly and the water and oil contact angle data for the polypropylene surface are shown in Table 1.

[0108] Example 5 Based on 100 parts by mass of the polypropylene surface sample (surface sample 2), 2-acrylamido-2-methylpropanesulfonic acid (10 parts by mass) was dissolved in acetone (50 parts by mass) to obtain an acetone solution of 2-acrylamido-2-methylpropanesulfonic acid; potassium hydroxide (6 parts by mass) was dissolved in deionized water (50 parts by mass) to obtain an aqueous potassium hydroxide solution; the acetone solution of 2-acrylamido-2-methylpropanesulfonic acid was added to the polypropylene surface sample under vacuum to thoroughly contact and mix them; and the mixture was then dried (dried in a blast drying oven at 80°C). After drying, the dried mixture of 2-acrylamido-2-methylpropanesulfonic acid and polypropylene surface sample was irradiated with microwaves for 3 minutes under nitrogen atmosphere (power 1000W); the product after microwave irradiation was immersed in deionized water for 10 minutes, and the deionized water was replaced three times repeatedly to ensure the removal of 2-acrylamido-2-methylpropanesulfonic acid monomers that were not involved in the grafting reaction, and then placed in a blast drying oven at 80 ° C to dry, thereby obtaining a dried 2-acrylamido-2-methylpropanesulfonic acid grafted polypropylene surface sample; the potassium hydroxide aqueous solution was thoroughly contacted and mixed with the dried 2-acrylamido-2-methylpropanesulfonic acid grafted polypropylene surface sample under vacuum; after the addition of the potassium hydroxide aqueous solution was completed, the mixing and reaction were continued for another 5 minutes. After the reaction was completed, the reaction product was washed with deionized water according to the same washing steps as above, and then placed in a blast drying oven at 80 ° C to dry, thereby obtaining a polypropylene surface sample grafted with potassium 2-acrylamido-2-methylpropanesulfonic acid.

[0109] Based on 100 parts by mass of the polypropylene surface sample, vinyl hydrogen-containing silicone oil (9 parts by mass) was dissolved in ethanol (50 parts by mass) to obtain an ethanol solution of vinyl hydrogen-containing silicone oil; sodium chloride (4 parts by mass) was dissolved in deionized water (50 parts by mass) to obtain an aqueous sodium chloride solution; the ethanol solution of vinyl hydrogen-containing silicone oil was added under vacuum to the polypropylene surface sample grafted with potassium 2-acrylamido-2-methylpropanesulfonate to thoroughly contact and mix them, and then the mixture was dried (dried in a blast drying oven at 80°C); after drying, the vinyl hydrogen-containing silicone oil and the grafted polypropylene were mixed. The dried mixture with the surface sample was thoroughly mixed by contacting with an aqueous sodium chloride solution, then the mixture was dried (dried in a blast drying oven at 80 ° C); the dried mixture was irradiated with microwaves for 3 minutes under nitrogen atmosphere (power 1000 W); the material after the microwave irradiation was immersed in deionized water for 10 minutes, and the deionized water was replaced three times repeatedly to ensure the removal of the vinyl hydrogen-containing silicone oil monomer and sodium chloride that were not involved in the grafting reaction, and then placed in a blast drying oven at 80 ° C and dried; thereby obtaining a super-wetting surface sample grafted with potassium 2-acrylamido-2-methylpropanesulfonate side groups and vinyl hydrogen-containing silicone oil side groups. The water contact angle and oil contact angle as well as the surface grafting rate data of the obtained super-wetting surface are shown in Table 1.

[0110] Example 6 Based on 100 parts by mass of the polypropylene surface sample (same as in Example 5), 2-acrylamido-2-methylpropanesulfonic acid (10 parts by mass) was dissolved in acetone (50 parts by mass) to obtain an acetone solution of 2-acrylamido-2-methylpropanesulfonic acid; potassium hydroxide (6 parts by mass) was dissolved in deionized water (50 parts by mass) to obtain an aqueous potassium hydroxide solution; the acetone solution of 2-acrylamido-2-methylpropanesulfonic acid was added to the polypropylene surface sample under vacuum to thoroughly contact and mix them, and then the mixture was dried (dried in a blast drying oven at 80°C). After drying, the dried mixture of 2-acrylamido-2-methylpropanesulfonic acid and polypropylene surface sample was irradiated with microwaves under nitrogen atmosphere for 3 minutes (power 1000W); the product after microwave irradiation was immersed in deionized water for 10 minutes, and the deionized water was replaced three times repeatedly to ensure the removal of 2-acrylamido-2-methylpropanesulfonic acid monomers that were not involved in the grafting reaction, and then placed in a blast drying oven at 80 °C to dry, obtaining a dried 2-acrylamido-2-methylpropanesulfonic acid grafted polypropylene surface sample; potassium hydroxide aqueous solution was added to the dried 2-acrylamido-2-methylpropanesulfonic acid grafted polypropylene surface sample under vacuum to bring them into contact and mix thoroughly; after the addition of potassium hydroxide aqueous solution was completed, further mixing and reaction was continued for 5 minutes. After the reaction was completed, the reaction product was washed with deionized water according to the same washing steps as above, and then placed in a blast drying oven at 80 °C to dry, thereby obtaining a super-wet surface sample grafted with potassium 2-acrylamido-2-methylpropanesulfonic acid side groups. The water and oil contact angles and surface grafting ratio data for the resulting superwetting surfaces are shown in Table 1.

[0111] Example 7 Based on 100 parts by mass of the polypropylene surface sample (same as in Example 5), methacrylic acid (10 parts by mass) was dissolved in acetone (50 parts by mass) to obtain an acetone solution of methacrylic acid; calcium hydroxide (8 parts by mass) was dissolved in deionized water (50 parts by mass) to obtain an aqueous calcium hydroxide solution; the acetone solution of methacrylic acid was added to the polypropylene surface sample under vacuum to thoroughly contact and mix them, and then the mixture was dried (dried in a blast drying oven at 80°C). After drying, the dried mixture of methacrylic acid and polypropylene surface sample was irradiated with microwaves under nitrogen atmosphere for 1 minute (power 2000W); the product after microwave irradiation was immersed in deionized water for 10 minutes, and the deionized water was replaced three times repeatedly to ensure the removal of methacrylic acid monomers that were not involved in the grafting reaction, and then placed in a blast drying oven at 80 ° C to dry, obtaining a dried methacrylic acid grafted polypropylene surface sample; calcium hydroxide aqueous solution was added to the dried methacrylic acid grafted polypropylene surface sample under vacuum to bring them into contact and mix thoroughly; after the addition of calcium hydroxide aqueous solution was completed, the mixing and reaction was continued for another 5 minutes. After the reaction was completed, the reaction product was washed with deionized water according to the same washing steps as above, and then placed in a blast drying oven at 80 ° C to dry, thereby obtaining a calcium methacrylate grafted polypropylene surface sample.

[0112] Based on 100 parts by mass of the polypropylene surface sample, 8 parts by mass of divinyl silicone oil was dissolved in 50 parts by mass of ethanol to obtain an ethanol solution of divinyl silicone oil; 6 parts by mass of sodium chloride was dissolved in 50 parts by mass of deionized water to obtain an aqueous sodium chloride solution; the ethanol solution of divinyl silicone oil was added to the above potassium methacrylate grafted polypropylene surface sample under vacuum to thoroughly contact and mix them, and then the mixture was dried (dried in a blast drying oven at 80°C); after drying, the divinyl silicone oil and the grafted polypropylene surface sample and The dried mixture was thoroughly mixed with an aqueous sodium chloride solution by contacting it with it, then the mixture was dried (dried in a blast drying oven at 80°C); the dried mixture was irradiated with microwaves for 1 minute under a nitrogen atmosphere (power 2000W); the material after the microwave irradiation was immersed in deionized water for 10 minutes, and the deionized water was replaced three times repeatedly to ensure the removal of the divinyl silicone oil monomer and sodium chloride that were not involved in the grafting reaction, and then dried in a blast drying oven at 80°C; a polypropylene superwetting surface sample grafted with calcium methacrylate side groups and divinyl silicone oil side groups was obtained. The water contact angle and oil contact angle as well as the surface grafting rate data of the resulting superwetting surface are shown in Table 1.

[0113] Example 8 Based on 100 parts by mass of the polypropylene surface sample (same as in Example 5), methacrylic acid (10 parts by mass) was dissolved in acetone (50 parts by mass) to obtain an acetone solution of methacrylic acid; calcium hydroxide (8 parts by mass) was dissolved in deionized water (50 parts by mass) to obtain an aqueous calcium hydroxide solution; the acetone solution of methacrylic acid was added to the polypropylene surface sample under vacuum to thoroughly contact and mix them, and then the mixture was dried (dried in a blast drying oven at 80°C). After drying, the dried mixture of methacrylic acid and polypropylene surface sample was irradiated with microwaves under nitrogen atmosphere for 1 minute (power 2000W); the product after microwave irradiation was immersed in deionized water for 10 minutes, and the deionized water was replaced three times repeatedly to ensure the removal of methacrylic acid monomers that were not involved in the grafting reaction, and then placed in a blast drying oven at 80 °C to dry, obtaining a dried methacrylic acid grafted polypropylene surface sample; calcium hydroxide aqueous solution was added to the dried methacrylic acid grafted polypropylene surface sample under vacuum to bring them into contact and mix thoroughly; after the addition of calcium hydroxide aqueous solution was completed, the mixing and reaction was continued for another 5 minutes. After the reaction was completed, the reaction product was washed with deionized water according to the same washing steps as above, and then placed in a blast drying oven at 80 °C to dry, thereby obtaining a polypropylene superwet surface sample grafted with calcium methacrylate side groups. The water contact angle and oil contact angle as well as the surface grafting rate data of the obtained superwet surface are shown in Table 1.

[0114] Comparative Example 2 A polypropylene surface sample (same as in Example 5) was tested directly and the water and oil contact angle data for the polypropylene surface are shown in Table 1.

[0115] Example 9 Based on 100 parts by mass of the polypropylene surface sample (surface sample 3), methacrylic acid (6 parts by mass) was dissolved in acetone (50 parts by mass) to obtain an acetone solution of methacrylic acid; the acetone solution of methacrylic acid was added to the polypropylene surface sample under vacuum to thoroughly contact and mix them, and then the mixture was dried (dried in a blast drying oven at 80 ° C). After drying, the dried mixture of methacrylic acid and polypropylene surface sample was irradiated with microwaves for 30 minutes under a nitrogen atmosphere (power 500 W); the product after the microwave irradiation was immersed in deionized water for 10 minutes, and the deionized water was replaced three times repeatedly to ensure the removal of methacrylic acid monomers that were not involved in the graft reaction, and then dried in a blast drying oven at 80 ° C to obtain a dried methacrylic acid grafted polypropylene surface sample.

[0116] Based on 100 parts by mass of the polypropylene surface sample, divinyl silicone oil (10 parts by mass) was dissolved in ethanol (50 parts by mass) to obtain an ethanol solution of divinyl silicone oil; sodium chloride (6 parts by mass) was dissolved in deionized water (50 parts by mass) to obtain an aqueous sodium chloride solution; the ethanol solution of divinyl silicone oil was added to the above methacrylic acid grafted polypropylene surface sample under vacuum to thoroughly contact and mix them, and then the mixture was dried (dried in a blast drying oven at 80°C); after drying, the divinyl silicone oil and the grafted polypropylene surface sample were mixed. The dried mixture of polypropylene and methacrylic acid was thoroughly mixed with an aqueous sodium chloride solution, and then the mixture was dried (dried in a blast drying oven at 80 ° C); the dried mixture was irradiated with microwaves for 30 minutes under a nitrogen atmosphere (power 500 W); the material after the microwave irradiation was immersed in deionized water for 10 minutes, and the deionized water was replaced three times repeatedly to ensure the removal of the divinyl silicone oil monomer and sodium chloride that were not involved in the grafting reaction, and then dried in a blast drying oven at 80 ° C; a polypropylene superwetting surface sample grafted with methacrylic acid and divinyl silicone oil was obtained. The water contact angle and oil contact angle as well as the surface grafting rate data of the obtained superwetting surface are shown in Table 1.

[0117] Example 10 Based on 100 parts by mass of the polypropylene surface sample (same as in Example 9), methacrylic acid (1 part by mass) was dissolved in acetone (50 parts by mass) to obtain an acetone solution of methacrylic acid; the acetone solution of methacrylic acid was added to the polypropylene surface sample under vacuum, and they were thoroughly contacted and mixed, and then the mixture was dried (dried in a blast drying oven at 80 ° C). After drying, the dried mixture of methacrylic acid and polypropylene surface sample was irradiated with microwaves for 30 minutes under a nitrogen atmosphere (power 500 W); the product after the microwave irradiation was immersed in deionized water for 10 minutes, and the deionized water was replaced three times repeatedly to ensure the removal of methacrylic acid monomers that were not involved in the graft reaction, and then dried in a blast drying oven at 80 ° C to obtain a dried methacrylic acid-grafted polypropylene surface sample.

[0118] Based on 100 parts by mass of the polypropylene surface sample, methylvinylsilicone oil (2 parts by mass) was dissolved in ethanol (50 parts by mass) to obtain an ethanol solution of methylvinylsilicone oil; an aqueous solution of graphene oxide (GO) (10 parts by mass) and ascorbic acid (1 part by mass) were dissolved in deionized water (50 parts by mass) to obtain a dispersion of graphene oxide (GO); the ethanol solution of methylvinylsilicone oil was added to the above methacrylic acid grafted polypropylene surface sample under vacuum to thoroughly contact and mix them, and then the mixture was dried (dried in a blast drying oven at 80°C); after drying, the dried powder of the mixture of methylvinylsilicone oil and the grafted polypropylene surface sample was thoroughly contacted and mixed with the dispersion of graphene oxide (GO), and then the mixture was dried (dried in a blast drying oven at 80°C), where the graphene oxide and the ascorbic acid were mixed. A dispersion of graphene oxide was formed by mixing methacrylic acid and deionized water, the dispersion of graphene oxide was mixed with a mixture of methylvinylsilicone oil and grafted polypropylene surface sample, and oven-dried at 80 °C. Ascorbic acid was used as a reducing agent for graphene oxide to reduce it to graphene, where graphene is the microwave absorbing medium for the subsequent grafting step by microwave irradiation; the dried mixture was irradiated with microwaves for 30 minutes under a nitrogen atmosphere (power 500 W); after the end of microwave irradiation, the material was immersed in deionized water for 10 minutes and the deionized water was replaced three times repeatedly to ensure the removal of methylvinylsilicone oil monomer and graphene oxide that were not involved in the grafting reaction, and then placed in a blast drying oven at 80 °C to dry; a polypropylene superwet surface sample grafted with methacrylic acid side groups and methylvinylsilicone oil side groups was obtained. The water contact angle and oil contact angle as well as the surface grafting rate data of the obtained superwet surface are shown in Table 1.

[0119] Example 11 Based on 100 parts by mass of the polypropylene surface sample (same as in Example 9), methacrylic acid (7 parts by mass) was dissolved in acetone (50 parts by mass) to obtain an acetone solution of methacrylic acid; the acetone solution of methacrylic acid was added to the polypropylene surface sample under vacuum, and they were thoroughly contacted and mixed, and then the mixture was dried (dried in a blast drying oven at 80 ° C). After drying, the dried mixture of methacrylic acid and polypropylene surface sample was irradiated with microwaves for 30 minutes under a nitrogen atmosphere (power 500 W); the product after the microwave irradiation was immersed in deionized water for 10 minutes, and the deionized water was replaced three times repeatedly to ensure the removal of methacrylic acid monomers that were not involved in the graft reaction, and then placed in a blast drying oven at 80 ° C to dry, thereby obtaining a dried methacrylic acid-grafted polypropylene surface sample.

[0120] Based on 100 parts by mass of the polypropylene surface sample, methylvinyl silicone oil (8 parts by mass) was dissolved in ethanol (50 parts by mass) to obtain an ethanol solution of methylvinyl silicone oil; an aqueous solution of graphene oxide (GO) (3 parts by mass) and ascorbic acid (0.3 parts by mass) were dissolved in deionized water (50 parts by mass) to obtain a dispersion of graphene oxide (GO); the ethanol solution of methylvinyl silicone oil was added to the above methacrylic acid grafted polypropylene surface sample under vacuum to thoroughly contact and mix them, and then the mixture was dried (dried in a blast drying oven at 80°C); after drying, the dried mixture of methylvinyl silicone oil and the grafted polypropylene surface sample was thoroughly contacted and mixed with the dispersion of graphene oxide (GO), and then the mixture was dried (dried in a blast drying oven at 80°C), where the graphene oxide and the ascorbic acid were mixed. A dispersion of graphene oxide was formed by mixing ascorbic acid with deionized water, the dispersion of graphene oxide was mixed with a mixture of methylvinylsilicone oil and grafted polypropylene surface sample, and oven-dried at 80 °C. Ascorbic acid was used as a reducing agent for graphene oxide to reduce it to graphene, which is the microwave absorbing medium for the subsequent grafting process by microwave irradiation; the dried mixture was irradiated with microwaves for 30 minutes under a nitrogen atmosphere (power 500 W); after the microwave irradiation, the material was immersed in deionized water for 10 minutes and the deionized water was replaced three times repeatedly to ensure the removal of methylvinylsilicone oil monomer and graphene oxide that were not involved in the grafting reaction, and then placed in a blast drying oven at 80 °C to dry; a polypropylene superwet surface sample grafted with methacrylic acid and methylvinylsilicone oil was obtained. The water contact angle and oil contact angle data of the obtained superwet surface are shown in Table 1.

[0121] Example 12 Based on 100 parts by mass of the polypropylene surface sample (same as in Example 9), vinyltrimethoxysilane (9 parts by mass) was dissolved in ethanol (50 parts by mass) to obtain an ethanol solution of vinyltrimethoxysilane; sodium chloride (3 parts by mass) was dissolved in deionized water (50 parts by mass) to obtain an aqueous sodium chloride solution; the ethanol solution of vinyltrimethoxysilane was added to the polypropylene surface sample under vacuum to thoroughly contact and mix them, and then the mixture was dried (dried in a blast drying oven at 80°C). After drying, the dried mixture of vinyltrimethoxysilane and polypropylene surface sample was thoroughly mixed by contacting with an aqueous sodium chloride solution, and then the mixture was dried (dried in a blast drying oven at 80°C); after drying, the dried mixture of vinyltrimethoxysilane and polypropylene surface sample was irradiated with microwaves for 30 minutes under a nitrogen atmosphere (power 500W); after the microwave irradiation was completed, the product was immersed in deionized water for 10 minutes, and the deionized water was replaced three times to ensure that the vinyltrimethoxysilane monomer and sodium chloride not involved in the grafting reaction were removed, and then the product was dried in a blast drying oven at 80°C to obtain a dried vinyltrimethoxysilane-grafted polypropylene surface sample.

[0122] Based on 100 parts by mass of the polypropylene surface sample, styrene (8 parts by mass) was dissolved in ethanol (50 parts by mass) to obtain an ethanol solution of styrene; an aqueous solution of graphene oxide (GO) (4 parts by mass) and ascorbic acid (0.4 parts by mass) were dissolved in deionized water (50 parts by mass) to obtain a dispersion of graphene oxide (GO); the ethanol solution of styrene was added to the above styrene-grafted polypropylene surface sample under vacuum to thoroughly contact and mix them, and then the mixture was dried (dried in a blast drying oven at 80°C); after drying, the dried powder of the mixture of styrene and the grafted polypropylene surface sample was thoroughly contacted and mixed with the dispersion of graphene oxide (GO), and then the mixture was dried (dried in a blast drying oven at 80°C), where the graphene oxide, ascorbic acid, and deionized water were mixed. The graphene oxide dispersion was formed by mixing with styrene and water, the graphene oxide dispersion was mixed with a mixture of styrene and grafted polypropylene surface sample, and oven-dried at 80 ° C., and ascorbic acid was used as a reducing agent for graphene oxide to reduce the graphene oxide to graphene, where graphene is a microwave absorbing medium for the subsequent grafting process by microwave irradiation; the dried mixture was irradiated with microwaves for 30 minutes under a nitrogen atmosphere (power 500 W); the material after the microwave irradiation was immersed in deionized water for 10 minutes and the deionized water was replaced three times repeatedly to ensure the removal of styrene monomer and graphene oxide that were not involved in the grafting reaction, and then placed in a blast drying oven at 80 ° C. to dry; an amphiphilic polypropylene surface sample grafted with vinyltrimethoxysilane and styrene was obtained. The data of the water contact angle and oil contact angle as well as the surface grafting rate of the obtained amphiphilic polypropylene surface are shown in Table 1.

[0123] Comparative Example 3 A polypropylene surface sample (same as in Example 9) was tested directly and the water and oil contact angle data for the polypropylene surface are shown in Table 1.

[0124] [Table 1]

[0125] From Table 1 it can be seen that the superwetting surfaces obtained after hydrophilic graft modification or further oleophilic graft modification of the polypropylene surface according to the invention achieved a significant increase in hydrophilicity and oleophilicity compared to the unmodified polypropylene surface, and that said superwetting surfaces achieved superhydrophilic, oleophilic or even in some cases both superhydrophilic and superoleophilic (superamphiphilic) properties, indicating that a very effective amphiphilic modification of the polypropylene surface was achieved.

[0126] Example 13 Based on 100 parts by mass of a polypropylene porous membrane (specification 1: average pore size 0.8 μm, porosity 80%; surface sample 4), maleic anhydride (5 parts by mass) was dissolved in acetone (50 parts by mass) to obtain an acetone solution of maleic anhydride; sodium hydroxide (5 parts by mass) was dissolved in deionized water (50 parts by mass) to obtain an aqueous sodium hydroxide solution; the acetone solution of maleic anhydride was added to the polypropylene porous membrane under vacuum with mechanical stirring to mix them thoroughly, and then the mixture was dried (dried in a blast drying oven at 80° C.). After drying, the dried mixture of maleic anhydride and polypropylene porous membrane was irradiated with microwaves under nitrogen atmosphere for 5 minutes (power 700W); the product after microwave irradiation was immersed in deionized water for 10 minutes, and the deionized water was replaced three times repeatedly to ensure the removal of maleic anhydride monomers that were not involved in the grafting reaction, and then the membrane was placed in a blast drying oven at 80°C to dry, obtaining a dried maleic anhydride grafted polypropylene porous membrane; the sodium hydroxide aqueous solution was thoroughly mixed with the dried maleic anhydride grafted polypropylene porous membrane under vacuum with stirring; after the addition of the sodium hydroxide aqueous solution was completed, the mixing and reaction was continued for 5 minutes with further stirring. After the reaction was completed, the reaction product was washed with deionized water according to the same washing steps as above, and then placed in a blast drying oven at 80°C to dry, thereby obtaining a sodium maleate grafted polypropylene porous membrane.

[0127] Based on 100 parts by mass of the polypropylene porous membrane, vinyl silicone oil (5 parts by mass) was dissolved in ethanol (50 parts by mass) to obtain an ethanol solution of vinyl silicone oil; sodium chloride (5 parts by mass) was dissolved in deionized water (50 parts by mass) to obtain an aqueous sodium chloride solution; the ethanol solution of vinyl silicone oil was added to the sodium maleate-grafted polypropylene porous membrane obtained above with mechanical stirring under vacuum to mix them thoroughly, and then the mixture was dried (dried in a blast drying oven at 80°C); after drying, the vinyl silicone oil and the sodium maleate-grafted polypropylene porous membrane were mixed. The dried powder of the mixture was thoroughly mixed with an aqueous sodium chloride solution, and then the mixture was dried (dried in a blast drying oven at 80 ° C); the dried mixture was irradiated with microwaves for 5 minutes under nitrogen atmosphere (power 700 W); the material after the microwave irradiation was immersed in deionized water for 10 minutes, and the deionized water was replaced three times repeatedly to ensure the removal of vinyl silicone monomer and sodium chloride that were not involved in the grafting reaction; then the resulting polypropylene porous membrane was placed in a blast drying oven at 80 ° C to dry, and an amphiphilic polypropylene porous membrane grafted with sodium maleate side groups and vinyl silicone oil side groups was obtained. The water contact angle and oil contact angle, water flux and oil flux, and surface grafting rate data of the resulting amphiphilic polypropylene porous membrane are shown in Table 2.

[0128] Example 14 Based on 100 parts by mass of a polypropylene porous membrane (the same as in Example 13), maleic anhydride (5 parts by mass) was dissolved in acetone (50 parts by mass) to obtain an acetone solution of maleic anhydride; sodium hydroxide (5 parts by mass) was dissolved in deionized water (50 parts by mass) to obtain an aqueous sodium hydroxide solution; the acetone solution of maleic anhydride was added to the polypropylene porous membrane under vacuum with mechanical stirring to mix them thoroughly, and then the mixture was dried (dried in a blast drying oven at 80°C). After drying, the dried mixture of maleic anhydride and polypropylene porous membrane was irradiated with microwaves under nitrogen atmosphere for 5 minutes (power 700W); the product after microwave irradiation was immersed in deionized water for 10 minutes, and the deionized water was replaced three times repeatedly to ensure the removal of maleic anhydride monomers that were not involved in the grafting reaction, and then the membrane was placed in a blast drying oven at 80 ° C to dry, obtaining a dried maleic anhydride grafted polypropylene porous membrane; sodium hydroxide aqueous solution was added to the dried maleic anhydride grafted polypropylene porous membrane under vacuum with stirring to mix them thoroughly; after the addition of sodium hydroxide aqueous solution was completed, the mixing and reaction was continued with further stirring for 5 minutes. After the reaction was completed, the reaction product was washed with deionized water according to the same washing steps as above, and then placed in a blast drying oven at 80 ° C to dry, thereby obtaining an amphiphilic polypropylene porous membrane grafted with sodium maleate side groups. The data of water and oil contact angles, water and oil fluxes, and surface grafting rate of the obtained amphiphilic polypropylene porous membrane are shown in Table 2.

[0129] Example 15 Based on 100 parts by weight of polypropylene porous membrane (same as in Example 13), vinyl silicone oil (10 parts by weight) is dissolved in ethanol (50 parts by weight) to obtain an ethanol solution of vinyl silicone oil; sodium chloride (5 parts by weight) is dissolved in deionized water (50 parts by weight) to obtain an aqueous sodium chloride solution; the ethanol solution of vinyl silicone oil is added to the polypropylene porous membrane under vacuum with mechanical stirring, and they are thoroughly mixed, and then the mixture is dried (dried in a blast drying oven at 80 ° C); after drying, the dried powder of the mixture of vinyl silicone oil and polypropylene porous membrane is thoroughly mixed with an aqueous sodium chloride solution, and then the mixture is dried (dried in a blast drying oven at 80 ° C); the dried mixture is irradiated with microwaves for 3 minutes under nitrogen atmosphere (power 1000 W); the material after microwave irradiation is immersed in deionized water for 10 minutes, and the deionized water is replaced three times repeatedly to ensure that the vinyl silicone monomer and sodium chloride that are not involved in the grafting reaction are removed, and then it is put into a blast drying oven at 80 ° C to dry, thereby obtaining an amphiphilic polypropylene porous membrane grafted with vinyl silicone oil side groups.

[0130] Based on 100 parts by mass of the polypropylene porous membrane, acrylic acid (10 parts by mass) was dissolved in acetone (50 parts by mass) to obtain an acetone solution of acrylic acid; potassium hydroxide (8 parts by mass) was dissolved in deionized water (50 parts by mass) to obtain an aqueous potassium hydroxide solution; the acetone solution of acrylic acid was added to the polypropylene porous membrane grafted with the vinyl silicone oil side group described above with mechanical stirring under vacuum to mix them thoroughly, and then the mixture was dried (dried in a blast drying oven at 80°C). After drying, the dried mixture of acrylic acid and grafted polypropylene porous membrane was irradiated with microwaves under nitrogen atmosphere for 3 minutes (power 1000W); the product after microwave irradiation was immersed in deionized water for 10 minutes, and the deionized water was replaced three times repeatedly to ensure the removal of acrylic acid monomers that were not involved in the grafting reaction, and then placed in a blast drying oven at 80 ° C to dry, obtaining a dried polypropylene porous membrane grafted with acrylic acid and vinyl silicone oil; potassium hydroxide aqueous solution was added to the dried polypropylene porous membrane grafted with acrylic acid and vinyl silicone oil under vacuum with stirring to mix them thoroughly; after the addition of potassium hydroxide aqueous solution was completed, the mixing and reaction was continued with further stirring for 5 minutes. After the reaction was completed, the reaction product was washed with deionized water according to the same washing steps as above, and then placed in a blast drying oven at 80 ° C to dry, thereby obtaining an amphiphilic polypropylene porous membrane grafted with potassium acrylate side groups and vinyl silicone oil side groups. The data of the water contact angle, oil contact angle, water flux, oil flux, and surface graft ratio of the obtained amphiphilic polypropylene porous membrane are shown in Table 2.

[0131] Example 16 Based on 100 parts by mass of a polypropylene porous membrane (the same as in Example 13), acrylic acid (10 parts by mass) was dissolved in acetone (50 parts by mass) to obtain an acetone solution of acrylic acid; potassium hydroxide (8 parts by mass) was dissolved in deionized water (50 parts by mass) to obtain an aqueous potassium hydroxide solution; the acetone solution of acrylic acid was added to the polypropylene porous membrane under vacuum with mechanical stirring to mix them thoroughly, and then the mixture was dried (dried in a blast drying oven at 80°C). After drying, the dried mixture of acrylic acid and polypropylene porous membrane was irradiated with microwaves under nitrogen atmosphere for 3 minutes (power 1000W); the product after microwave irradiation was immersed in deionized water for 10 minutes, and the deionized water was replaced three times repeatedly to ensure the removal of acrylic acid monomers that were not involved in the grafting reaction, and then the membrane was placed in a blast drying oven at 80 ° C to dry, obtaining a dried acrylic acid grafted polypropylene porous membrane; potassium hydroxide aqueous solution was added to the dried acrylic acid grafted polypropylene porous membrane under vacuum with stirring to mix them thoroughly; after the addition of potassium hydroxide aqueous solution was completed, the mixing and reaction was continued with further stirring for 5 minutes. After the reaction was completed, the reaction product was washed with deionized water according to the same washing steps as above, and then placed in a blast drying oven at 80 ° C to dry, thereby obtaining an amphiphilic polypropylene porous membrane grafted with potassium acrylate side groups. The data of water and oil contact angles, water and oil fluxes, and surface grafting rate of the obtained amphiphilic polypropylene porous membrane are shown in Table 2.

[0132] Comparative Example 4 A polypropylene porous membrane (same as in Example 13) was directly tested, and the data of water and oil contact angles and water and oil flux of the polypropylene porous membrane are shown in Table 2.

[0133] Example 17 Based on 100 parts by mass of polypropylene porous membrane (specification 2: average pore size 0.65 μm, porosity 70%; surface sample 5), 2-acrylamido-2-methylpropanesulfonic acid (10 parts by mass) was dissolved in acetone (50 parts by mass) to obtain an acetone solution of 2-acrylamido-2-methylpropanesulfonic acid; potassium hydroxide (8 parts by mass) was dissolved in deionized water (50 parts by mass) to obtain an aqueous potassium hydroxide solution; the acetone solution of 2-acrylamido-2-methylpropanesulfonic acid was added to the polypropylene porous membrane under vacuum with mechanical stirring to mix them thoroughly; and the mixture was then dried (dried in a blast drying oven at 80 ° C). After drying, the dried mixture of 2-acrylamido-2-methylpropanesulfonic acid and polypropylene porous membrane was irradiated with microwaves for 3 minutes under nitrogen atmosphere (power 1000W); the product after microwave irradiation was immersed in deionized water for 10 minutes, and the deionized water was replaced three times repeatedly to ensure the removal of 2-acrylamido-2-methylpropanesulfonic acid monomers that were not involved in the grafting reaction, and then the membrane was placed in a blast drying oven at 80 ° C to dry, obtaining a dried 2-acrylamido-2-methylpropanesulfonic acid grafted polypropylene porous membrane; the potassium hydroxide aqueous solution was thoroughly mixed with the dried 2-acrylamido-2-methylpropanesulfonic acid grafted polypropylene porous membrane under vacuum with stirring; after the addition of the potassium hydroxide aqueous solution was completed, the mixing and reaction was continued for 5 minutes with further stirring. After the reaction was completed, the reaction product was washed with deionized water according to the same washing steps as above, and then placed in a blast drying oven at 80 ° C to dry, thereby obtaining a potassium 2-acrylamido-2-methylpropanesulfonic acid grafted polypropylene porous membrane.

[0134] Based on 100 parts by mass of the polypropylene porous membrane, vinyl hydrogen-containing silicone oil (10 parts by mass) was dissolved in ethanol (50 parts by mass) to obtain an ethanol solution of vinyl hydrogen-containing silicone oil; sodium chloride (5 parts by mass) was dissolved in deionized water (50 parts by mass) to obtain an aqueous sodium chloride solution; the ethanol solution of vinyl hydrogen-containing silicone oil was added to the above potassium 2-acrylamido-2-methylpropanesulfonate-grafted polypropylene porous membrane under vacuum with mechanical stirring to mix them thoroughly, and then the mixture was dried (dried in a blast drying oven at 80°C); after drying, the mixture of vinyl hydrogen-containing silicone oil and polypropylene porous membrane was The dried powder was thoroughly mixed with an aqueous sodium chloride solution, and then the mixture was dried (dried in a blast oven at 80°C); the dried mixture was irradiated with microwaves for 3 minutes under nitrogen atmosphere (power 1000W); the material after the microwave irradiation was immersed in deionized water for 10 minutes, and the deionized water was replaced three times repeatedly to ensure the removal of vinyl hydrogen-containing silicone oil monomers and sodium chloride that were not involved in the grafting reaction, and then the membrane was placed in a blast oven at 80°C to dry; thereby obtaining an amphiphilic polypropylene porous membrane grafted with sodium 2-acrylamido-2-methylpropanesulfonate side groups and vinyl hydrogen-containing silicone oil side groups. The water contact angle and oil contact angle, water flux and oil flux, and surface grafting rate data of the obtained amphiphilic polypropylene porous membrane are shown in Table 2.

[0135] Example 18 Based on 100 parts by mass of a polypropylene porous membrane (the same as in Example 17), 2-acrylamido-2-methylpropanesulfonic acid (10 parts by mass) was dissolved in acetone (50 parts by mass) to obtain an acetone solution of 2-acrylamido-2-methylpropanesulfonic acid; potassium hydroxide (8 parts by mass) was dissolved in deionized water (50 parts by mass) to obtain an aqueous potassium hydroxide solution; the acetone solution of 2-acrylamido-2-methylpropanesulfonic acid was added to the polypropylene porous membrane under vacuum with mechanical stirring to mix them thoroughly, and then the mixture was dried (dried in a blast drying oven at 80°C). After drying, the dried mixture of 2-acrylamido-2-methylpropanesulfonic acid and polypropylene porous membrane is irradiated with microwaves (power 1000W) under nitrogen atmosphere for 3 minutes; after microwave irradiation, the product is immersed in deionized water for 10 minutes, and the deionized water is replaced three times repeatedly to ensure the removal of 2-acrylamido-2-methylpropanesulfonic acid monomers that were not involved in the grafting reaction; then, the membrane is placed in a blast drying oven at 80°C to dry, and a dried 2-acrylamido-2-methylpropanesulfonic acid grafted polypropylene porous membrane is obtained; an aqueous potassium hydroxide solution is added to the dried 2-acrylamido-2-methylpropanesulfonic acid grafted polypropylene porous membrane under vacuum with stirring to mix them thoroughly; after the addition of the aqueous potassium hydroxide solution is completed, the mixing and reaction are continued for 5 minutes with further stirring. After the reaction was completed, the reaction product was washed with deionized water according to the same washing steps as above, and then dried in a blast drying oven at 80°C, thereby obtaining an amphiphilic polypropylene porous membrane grafted with potassium 2-acrylamido-2-methylpropanesulfonate side groups. The data of water and oil contact angles, water and oil fluxes, and surface grafting rate of the obtained amphiphilic polypropylene porous membrane are shown in Table 2.

[0136] Example 19 Based on 100 parts by mass of a polypropylene porous membrane (the same as in Example 17), methacrylic acid (8 parts by mass) was dissolved in acetone (50 parts by mass) to obtain an acetone solution of methacrylic acid; calcium hydroxide (6 parts by mass) was dissolved in deionized water (50 parts by mass) to obtain an aqueous calcium hydroxide solution; the acetone solution of methacrylic acid was added to the polypropylene porous membrane under vacuum with mechanical stirring to mix them thoroughly, and then the mixture was dried (dried in a blast drying oven at 80°C). After drying, the dried mixture of methacrylic acid and polypropylene porous membrane is irradiated with microwaves under nitrogen atmosphere for 1 minute (power 2000W); the product after microwave irradiation is immersed in deionized water for 10 minutes, and the deionized water is replaced three times repeatedly to ensure the removal of methacrylic acid monomers that were not involved in the grafting reaction, and then the membrane is placed in a blast drying oven at 80 ° C to dry, obtaining a dried methacrylic acid grafted polypropylene porous membrane; calcium hydroxide aqueous solution is added to the dried methacrylic acid grafted polypropylene porous membrane under vacuum with stirring to mix them thoroughly; after the addition of calcium hydroxide aqueous solution is completed, the mixing and reaction are continued with further stirring for 5 minutes. After the reaction is completed, the reaction product is washed with deionized water according to the same washing steps as above, and then placed in a blast drying oven at 80 ° C to dry, thereby obtaining a calcium methacrylate grafted polypropylene porous membrane.

[0137] Based on 100 parts by mass of the polypropylene porous membrane, divinyl silicone oil (10 parts by mass) was dissolved in ethanol (50 parts by mass) to obtain an ethanol solution of divinyl silicone oil; sodium chloride (5 parts by mass) was dissolved in deionized water (50 parts by mass) to obtain an aqueous sodium chloride solution; the ethanol solution of divinyl silicone oil was added to the calcium methacrylate-grafted polypropylene porous membrane under vacuum with mechanical stirring to mix them thoroughly, and then the mixture was dried (dried in a blast drying oven at 80°C); after drying, the divinyl silicone oil and the grafted polypropylene porous membrane were dried. The mixture was thoroughly mixed with aqueous sodium chloride, then the mixture was dried (dried in a blast oven at 80°C); the dried mixture was irradiated with microwaves for 1 minute under nitrogen atmosphere (power 2000W); the material after microwave irradiation was immersed in deionized water for 10 minutes, and the deionized water was replaced three times repeatedly to ensure the removal of divinyl silicone oil monomer and sodium chloride that were not involved in the grafting reaction, and then the membrane was placed in a blast oven at 80°C to dry, thereby obtaining an amphiphilic polypropylene porous membrane grafted with calcium methacrylate side groups and divinyl silicone oil side groups. The data of water contact angle and oil contact angle, water flux and oil flux, and surface grafting rate of the obtained amphiphilic polypropylene porous membrane are shown in Table 2.

[0138] Example 20 Based on 100 parts by mass of a polypropylene porous membrane (the same as in Example 17), methacrylic acid (8 parts by mass) was dissolved in acetone (50 parts by mass) to obtain an acetone solution of methacrylic acid; calcium hydroxide (6 parts by mass) was dissolved in deionized water (50 parts by mass) to obtain an aqueous calcium hydroxide solution; the acetone solution of methacrylic acid was added to the polypropylene porous membrane under vacuum with mechanical stirring to mix them thoroughly, and then the mixture was dried (dried in a blast drying oven at 80°C). After drying, the dried mixture of methacrylic acid and polypropylene porous membrane was irradiated with microwaves under nitrogen atmosphere for 1 minute (power 2000W); the product after microwave irradiation was immersed in deionized water for 10 minutes, and the deionized water was replaced three times repeatedly to ensure the removal of methacrylic acid monomers that were not involved in the grafting reaction, and then the membrane was placed in a blast drying oven at 80 ° C to dry, obtaining a dried methacrylic acid grafted polypropylene porous membrane; calcium hydroxide aqueous solution was added to the dried methacrylic acid grafted polypropylene porous membrane under vacuum with stirring to mix them thoroughly; after the addition of calcium hydroxide aqueous solution was completed, the mixing and reaction was continued with further stirring for 5 minutes. After the reaction was completed, the reaction product was washed with deionized water according to the same washing steps as above, and then placed in a blast drying oven at 80 ° C to dry, thereby obtaining an amphiphilic polypropylene porous membrane grafted with calcium methacrylate side groups. The data of water and oil contact angles, water and oil fluxes, and surface grafting rate of the obtained amphiphilic polypropylene porous membrane are shown in Table 2.

[0139] Example 21 Based on 100 parts by mass of polypropylene porous membrane (same as in Example 17), methacrylic acid (8 parts by mass) was dissolved in acetone (50 parts by mass) to obtain an acetone solution of methacrylic acid; the acetone solution of methacrylic acid was added to the polypropylene porous membrane under vacuum with mechanical stirring to mix them thoroughly, and then the mixture was dried (dried in a blast drying oven at 80°C). After drying, the dried mixture of methacrylic acid and polypropylene porous membrane was irradiated with microwaves for 30 minutes under a nitrogen atmosphere (power 500W); the product after the microwave irradiation was immersed in deionized water for 10 minutes, and the deionized water was replaced three times repeatedly to ensure the removal of methacrylic acid monomer that was not involved in the grafting reaction, and the membrane was placed in a blast drying oven at 80°C to dry, obtaining a dried methacrylic acid-grafted polypropylene porous membrane.

[0140] Based on 100 parts by mass of the polypropylene porous membrane, divinyl silicone oil (10 parts by mass) was dissolved in ethanol (50 parts by mass) to obtain an ethanol solution of divinyl silicone oil; sodium chloride (5 parts by mass) was dissolved in deionized water (50 parts by mass) to obtain an aqueous sodium chloride solution; the ethanol solution of divinyl silicone oil was added to the above methacrylic acid grafted polypropylene porous membrane with mechanical stirring under vacuum to mix them thoroughly, and then the mixture was dried (dried in a blast drying oven at 80°C); after drying, the divinyl silicone oil and the grafted polypropylene porous membrane were dried. The mixture was thoroughly mixed with an aqueous sodium chloride solution, and then the mixture was dried (dried in a blast oven at 80°C); the dried mixture was irradiated with microwaves for 30 minutes under nitrogen atmosphere (power 500W); the material after the microwave irradiation was immersed in deionized water for 10 minutes, and the deionized water was replaced three times repeatedly to ensure the removal of divinyl silicone oil monomer and sodium chloride that were not involved in the grafting reaction, and then the membrane was placed in a blast oven at 80°C to dry, thereby obtaining an amphiphilic polypropylene porous membrane grafted with methacrylic acid side groups and divinyl silicone oil side groups. The data of the water contact angle and oil contact angle, water flux and oil flux, and surface grafting rate of the obtained amphiphilic polypropylene porous membrane are shown in Table 2.

[0141] Example 22 Based on 100 parts by mass of polypropylene porous membrane (same as in Example 17), methacrylic acid (8 parts by mass) was dissolved in acetone (50 parts by mass) to obtain an acetone solution of methacrylic acid; calcium hydroxide (5 parts by mass) was dissolved in deionized water (50 parts by mass) to obtain an aqueous calcium hydroxide solution; the acetone solution of methacrylic acid was added to the polypropylene porous membrane under vacuum with mechanical stirring to mix them thoroughly, and then the mixture was dried (dried in a blast drying oven at 80°C). After drying, the dried mixture of methacrylic acid and polypropylene porous membrane was irradiated with microwaves for 30 minutes under a nitrogen atmosphere (power 500W); the product after the microwave irradiation was immersed in deionized water for 10 minutes, and the deionized water was replaced three times repeatedly to ensure the removal of methacrylic acid monomers that were not involved in the grafting reaction, and then the membrane was placed in a blast drying oven at 80°C to dry, obtaining a dried methacrylic acid-grafted polypropylene porous membrane. The calcium hydroxide aqueous solution is added to the dried methacrylic acid grafted polypropylene porous membrane under vacuum with stirring to mix them thoroughly; after the addition of the calcium hydroxide aqueous solution is completed, the mixing and reaction is continued with further stirring for 5 minutes. After the reaction is completed, the reaction product is washed with deionized water according to the same washing steps as above, and then put into a blast drying oven at 80°C to dry, thereby obtaining a calcium methacrylic acid grafted polypropylene porous membrane.

[0142] Based on 100 parts by mass of the polypropylene porous membrane, methylvinyl silicone oil (10 parts by mass) was dissolved in ethanol (50 parts by mass) to obtain an ethanol solution of methylvinyl silicone oil; an aqueous solution of graphene oxide (GO) (5 parts by mass) and ascorbic acid (0.5 parts by mass) were dissolved in deionized water (50 parts by mass) to obtain a dispersion of graphene oxide (GO); the ethanol solution of methylvinyl silicone oil was added to the calcium methacrylate-grafted polypropylene porous membrane under vacuum with mechanical stirring to mix them thoroughly, and then the mixture was dried (dried in a blast drying oven at 80 ° C); after drying, the dried mixture of methylvinyl silicone oil and the grafted polypropylene porous membrane was thoroughly mixed with the dispersion of graphene oxide (GO), and then the mixture was dried (dried in a blast drying oven at 80 ° C), where the graphene oxide, ascorbic acid, The graphene oxide dispersion was formed by mixing with deionized water; the graphene oxide dispersion was mixed with a mixture of methylvinylsilicone oil and grafted polypropylene porous membrane, and oven-dried at 80°C, and ascorbic acid was used as a reducing agent for graphene oxide to reduce the graphene oxide to graphene, where graphene is a microwave absorbing medium for the subsequent grafting step by microwave irradiation; the above dried mixture was irradiated with microwaves for 30 minutes under a nitrogen atmosphere (power 500W); the material after the microwave irradiation was immersed in deionized water for 10 minutes, and the deionized water was replaced three times repeatedly to ensure the removal of the methylvinylsilicone oil monomer and graphene oxide that were not involved in the grafting reaction, and then the membrane was placed in a blast drying oven at 80°C to dry; an amphiphilic polypropylene porous membrane grafted with calcium methacrylate and methylvinylsilicone oil was obtained. The water contact angle and oil contact angle, water flux and oil flux, and surface grafting rate data of the obtained amphiphilic polypropylene porous membrane are shown in Table 2.

[0143] Example 23 Based on 100 parts by mass of a polypropylene porous membrane (the same as in Example 17), vinyltrimethoxysilane (10 parts by mass) was dissolved in ethanol (50 parts by mass) to obtain an ethanol solution of vinyltrimethoxysilane; sodium chloride (5 parts by mass) was dissolved in deionized water (50 parts by mass) to obtain an aqueous sodium chloride solution; the ethanol solution of vinyltrimethoxysilane was added to the polypropylene porous membrane under vacuum with mechanical stirring to mix them thoroughly, and then the mixture was dried (dried in a blast drying oven at 80°C). After drying, the dried mixture of vinyltrimethoxysilane and polypropylene porous membrane is thoroughly mixed with sodium chloride aqueous solution, and then the mixture is dried (dried in a blast drying oven at 80°C); after drying, the dried mixture of vinyltrimethoxysilane and polypropylene porous membrane is irradiated with microwaves (power 500W) under nitrogen atmosphere for 30 minutes; after microwave irradiation, the product is immersed in deionized water for 10 minutes, and the deionized water is replaced three times repeatedly to ensure that the vinyltrimethoxysilane monomer and sodium chloride that are not involved in the grafting reaction are removed, and then the membrane is placed in a blast drying oven at 80°C to dry, and a dried vinyltrimethoxysilane-grafted polypropylene porous membrane is obtained.

[0144] Based on 100 parts by mass of the polypropylene porous membrane, styrene (10 parts by mass) was dissolved in ethanol (50 parts by mass) to obtain an ethanol solution of styrene; an aqueous solution of graphene oxide (GO) (5 parts by mass) and ascorbic acid (0.5 parts by mass) were dissolved in deionized water (50 parts by mass) to obtain a dispersion of graphene oxide (GO); the ethanol solution of styrene was added to the above styrene-grafted polypropylene porous membrane under vacuum with mechanical stirring to mix them thoroughly, and then the mixture was dried (dried in a blast drying oven at 80°C); after drying, the dried powder of the mixture of styrene and the grafted polypropylene porous membrane was thoroughly mixed with the dispersion of graphene oxide (GO), and then the mixture was dried (dried in a blast drying oven at 80°C), where the graphene oxide, ascorbic acid, and deionized water were mixed. A graphene oxide dispersion was formed by mixing with water; the graphene oxide dispersion was mixed with a mixture of styrene and grafted polypropylene porous membrane, oven-dried at 80°C, and ascorbic acid was used as a reducing agent for graphene oxide to reduce the graphene oxide to graphene, where graphene is a microwave absorbing medium for the subsequent grafting step by microwave irradiation; the dried mixture was irradiated with microwaves for 30 minutes under a nitrogen atmosphere (power 500W); the material after the microwave irradiation was immersed in deionized water for 10 minutes and the deionized water was replaced three times repeatedly to ensure the removal of styrene monomer and graphene oxide that were not involved in the grafting reaction, and the membrane was placed in a blast drying oven at 80°C to dry; an amphiphilic polypropylene porous membrane grafted with vinyltrimethoxysilane and styrene was obtained. The water contact angle and oil contact angle, water flux and oil flux, and surface grafting rate data of the obtained amphiphilic polypropylene porous membrane are shown in Table 2.

[0145] Comparative Example 5 A polypropylene porous membrane (same as in Example 17) was directly tested, and the data of water and oil contact angles and water and oil flux of the polypropylene porous membrane are shown in Table 2.

[0146] [Table 2]

[0147] From Table 2 it can be seen that the superwetting surfaces obtained after hydrophilic graft modification or further oleophilic graft modification of the polypropylene porous membrane according to the present invention achieved a significant increase in both water and oil flux compared to the unmodified polypropylene porous membrane, and the modified polypropylene porous membranes also achieved superhydrophilic, oleophilic, or even in some cases both superhydrophilic and superoleophilic properties, indicating that a very effective amphiphilic modification of the polypropylene porous membrane was achieved.

Claims

1. A superwetting surface which is a micro-nanostructured polypropylene surface, said polypropylene surface being grafted with hydrophilic side groups and further grafted with lipophilic side groups; wherein the superwetting surface is at least superhydrophilic and does not contain residues of an initiator.

2. 2. The superwetting surface of claim 1, characterized in that the water contact angle of said superwetting surface is less than or equal to 10 degrees.

3. 3. The superwetting surface of claim 2, characterized in that the water contact angle of said superwetting surface is about 0 degrees.

4. The superwetting surface according to claim 1 or 2, characterized in that the feature size of the micro-nanostructures of the polypropylene surface as graft base is between 1 nm and 100 μm.

5. The superwetting surface of claim 4, wherein the micro-nanostructure is a structure generated on the polypropylene surface by a thermally induced phase separation process, a photolithography technique, a femtosecond laser processing technique, a plasma etching technique, an electrospinning method, nanoimprinting, nanocasting, an ultra-precision micromilling technique, or an electric arc.

6. 5. The superwetting surface according to claim 4, characterized in that the polypropylene surface as graft base is a polypropylene porous membrane, a polypropylene flat membrane or a polypropylene hollow fiber microporous membrane.

7. The ultra-wetting surface of claim 6, wherein the polypropylene porous membrane has an average pore size of less than 100 μm.

8. The ultra-wetting surface according to claim 6, characterized in that the porosity of the polypropylene porous membrane is 50 to 90%.

9. 9. The superwetting surface of claim 1, wherein the hydrophilic side groups comprise units formed from one or more monomers containing a heteroatom selected from the group consisting of oxygen, sulfur, nitrogen, silicon, halogens, and combinations or substitutes thereof, and containing a carbon-carbon double bond.

10. 10. The superwetting surface of claim 9, wherein the monomer is at least one selected from the group consisting of organic acids and their derivatives, and vinyl silanes.

11. The superwetting surface of claim 10, wherein the derivative of the organic acid is an anhydride, an ester, or a salt.

12. 11. The superwetting surface of claim 10, wherein the organic acid and its derivatives are selected from the group consisting of maleic anhydride and its derivatives, (meth)acrylic acid and its derivatives, vinyl acetate, alkenylsulfonic acid and its derivatives, vinylbenzoic acid and its derivatives, itaconic acid and its derivatives, oleic acid and its derivatives, arachidonic acid and its derivatives, and combinations thereof.

13. 13. The superwetting surface according to claim 12, characterized in that the derivative of (meth)acrylic acid is glycidyl methacrylate.

14. The superwetting surface of claim 10, wherein the derivative of the organic acid is a salt form of the organic acid.

15. The vinyl silane is one or more compounds represented by formula (1): CH 2 =CH-(CH 2 ) n SiX 3 Formula (1) 11. The superwetting surface of claim 10, wherein n=0-3, and each X is the same or different and independently represents a chloro group, a methoxy group, an ethoxy group, and an acetoxy group.

16. 10. The superwetting surface of claim 9, wherein the hydrophilic side groups comprise or consist of units formed from a salt of an organic acid.

17. 17. The superwetting surface of any one of claims 1 to 16, characterized in that the oleophilic side groups are selected from the group consisting of side groups formed from vinyl silicone oils, side groups formed from styrene, and combinations thereof.

18. 20. The superwetting surface of claim 17, wherein the vinyl silicone oil is selected from the group consisting of vinyl terminated silicone oils, high vinyl silicone oils, and combinations thereof.

19. 20. The superwetting surface of claim 17, wherein the vinyl silicone oil is selected from the group consisting of methyl vinyl silicone oil, vinyl hydrogen containing silicone oil, divinyl silicone oil, and combinations thereof.

20. A superwetting surface according to any one of the preceding claims, characterized in that the oil contact angle of the superwetting surface is less than 90°.

21. 21. The superwetting surface of claim 20, wherein the oil contact angle of the superwetting surface is about 0[deg.].

22. 2. A method for preparing a superwetting surface according to claim 1, comprising subjecting a monomer for forming a side group and a polypropylene surface having a micro-nano structure as a graft base to a graft reaction by microwave irradiation in the absence of an initiator.

23. 23. The method according to claim 22, characterized in that it comprises the approach of contacting and mixing the polypropylene surface with monomers for forming hydrophilic side groups and monomers for lipophilic side groups; and then subjecting the resulting mixture to microwave irradiation grafting without the addition of an initiator.

24. 23. The method according to claim 22, characterized in that it comprises the approach of contacting and mixing the polypropylene surface with monomers for forming hydrophilic side groups; then subjecting the resulting mixture to microwave irradiation grafting without the addition of an initiator; then mixing the resulting grafted product with monomers for forming oleophilic side groups and an inorganic microwave absorbing medium and microwave irradiation grafting without the addition of an initiator.

25. 23. The method according to claim 22, characterized in that it comprises the approach of contacting and mixing the polypropylene surface with a monomer for forming lipophilic side groups and an inorganic microwave absorbing medium, then subjecting the resulting mixture to microwave irradiation grafting without the addition of an initiator; then mixing the resulting grafted product with a monomer for forming hydrophilic side groups and microwave irradiation grafting without the addition of an initiator.

26. the monomer for forming the hydrophilic side group is at least one of an organic acid or an anhydride or ester thereof; 26. The method according to any one of claims 23 to 25, characterized in that the method further comprises the step of contacting and mixing the polypropylene surface grafted with at least one side group of an organic acid or an anhydride or ester thereof with a base.

27. 27. The method of claim 26, wherein the base is selected from the group consisting of metal hydroxides and aqueous ammonia.

28. 28. The method of claim 27, wherein the metal hydroxide is selected from the group consisting of sodium hydroxide, potassium hydroxide, barium hydroxide, lithium hydroxide, strontium hydroxide, calcium hydroxide, iron hydroxide, ferrous hydroxide, zinc hydroxide, magnesium hydroxide, cobalt hydroxide, gold hydroxide, aluminum hydroxide, copper hydroxide, beryllium hydroxide, rare earth hydroxides, and combinations thereof.

29. 27. The method of claim 26, wherein the amount of base is 0.1 to 10% by weight based on the amount of the polypropylene surface.

30. The method according to any one of claims 23 to 25, characterized in that at least one of the mixing processes is carried out under vacuum.

31. 31. The method according to any one of claims 23 to 30, characterized in that the amount of monomer for forming the hydrophilic side groups is 0.1 to 10% by weight based on the amount of the polypropylene surface.

32. 32. The method of claim 31, wherein the monomers for forming the hydrophilic side groups are used in the form of a solution in which the monomers are dissolved in one or more solvents, the solvents being selected from the group consisting of alcohols, ketones, esters, water and combinations thereof.

33. 33. The method according to any one of claims 23 to 32, characterized in that the amount of monomer for forming the lipophilic side groups is 0.1 to 30% by weight based on the amount of the polypropylene surface.

34. 34. The method of claim 33, wherein the monomers for forming the lipophilic side groups are used in the form of a solution in which the monomers are dissolved in one or more solvents, the solvents being selected from the group consisting of alcohols, ketones, esters, water and combinations thereof.

35. The method according to any one of claims 22 to 34, characterized in that an inorganic microwave absorbing medium is added.

36. 36. The method of claim 35, wherein the inorganic microwave absorbing medium is selected from the group consisting of metal hydroxides, metal salts, metal oxides, graphite materials, ferroelectric materials, electrolytic stones, chalcopyrites, and combinations thereof.

37. 37. The method of claim 36, wherein the metal hydroxide is selected from the group consisting of potassium hydroxide, barium hydroxide, sodium hydroxide, lithium hydroxide, strontium hydroxide, calcium hydroxide, iron hydroxide, ferrous hydroxide, zinc hydroxide, magnesium hydroxide, cobalt hydroxide, gold hydroxide, aluminum hydroxide, copper hydroxide, beryllium hydroxide, rare earth hydroxides, and combinations thereof.

38. 37. The method of claim 36, wherein the metal salt is selected from the group consisting of ammonium nitrate, potassium nitrate, sodium nitrate, barium nitrate, calcium nitrate, magnesium nitrate, aluminum nitrate, manganese nitrate, zinc nitrate, ferric nitrate, ferrous nitrate, copper nitrate, silver nitrate, ammonium chloride, potassium chloride, sodium chloride, barium chloride, calcium chloride, magnesium chloride, aluminum chloride, manganese chloride, zinc chloride, ferric chloride, ferrous chloride, copper chloride, ammonium sulfate, potassium sulfate, sodium sulfate, calcium sulfate, magnesium sulfate, aluminum sulfate, manganese sulfate, zinc sulfate, ferrous sulfate, ferrous sulfate, copper sulfate, silver sulfate, ammonium carbonate, potassium carbonate, sodium carbonate, magnesium carbonate, calcium carbonate, barium carbonate, potassium dihydrogen phosphate, barium titanate, strontium titanate, copper calcium titanate, and combinations thereof.

39. 37. The method of claim 36, wherein the metal oxide is selected from the group consisting of ferric oxide, ferric oxide, and combinations thereof.

40. 37. The method of claim 36, wherein the graphitic material is selected from the group consisting of carbon black, graphite powder, graphene, reduction products of graphene oxide, carbon nanotubes, activated carbon, and combinations thereof.

41. 36. The method of claim 35, wherein the amount of said inorganic microwave absorbing medium in one application is 0.1-10% by weight of the amount of said polypropylene surface.

42. 36. The method of claim 35, wherein the inorganic microwave absorbing medium is added directly or in the form of a solution or dispersion in which the inorganic microwave absorbing medium is dissolved or dispersed in one or more solvents, the one or more solvents being selected from the group consisting of alcohols, ketones, esters, water and combinations thereof.

43. 43. The method of claim 42, wherein the dispersion liquid includes a surfactant.

44. A superwetting surface prepared by the method of any one of claims 22 to 43.

45. An article comprising the superwetting surface of any one of claims 1 to 21, said article being a film.

46. ​​The article of claim 45, wherein the film is a polypropylene porous membrane, a polypropylene flat membrane or a polypropylene hollow fiber microporous membrane.

47. An article comprising the superwetting surface of any one of claims 1 to 21, the article being a sheet or plate.

48. An article comprising the superwetting surface of any one of claims 1 to 21, the article being a molded article.

49. An article comprising the ultra-wetting surface of any one of claims 1 to 21, the article being a plastic article.

50. An article comprising the ultra-wet surface of any one of claims 1 to 21, the article being the outer packaging of a food bag.

51. An article comprising the ultra-wet surface of any one of claims 1 to 21, the article being an automobile bumper.

52. Use of the article described in claim 49 in a bonding method.

53. Use of an article according to claim 50 or 51 in a spraying method.

54. Use of the article described in claim 46 in oil-water separation.

55. Use of the article of claim 46 in water treatment.

Citation Information

Patent Citations

  • Selective leucocyte trapper and leucocyte trapping apparatus

    JP1995024066A

  • Method for modifying the surface of an object

    WO1999024174A1